Gas Separation Membranes

The amine-containing polymeric membrane with hydrophilically modified carbon nanotubes enhances CO2/N2 separation in industrial gas streams by improving flux and selectivity, addressing the inefficiencies of existing technologies in CO2 removal from flue gas.

JP7611818B2Active Publication Date: 2025-01-10OHIO STATE INNOVATION FOUND
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021514356
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-14
Filing Date
2019-09-16
Publication Date
2025-01-10
Estimated Expiration
2039-09-16

AI Technical Summary

Technical Problem

Existing gas separation technologies face challenges in efficiently removing carbon dioxide and other gases like hydrogen sulfide and nitrogen oxides from industrial gas streams, particularly in applications such as flue gas from coal or natural gas combustion, where there is a need for improved membrane materials and methods to enhance CO2/N2 selectivity and flux.

Method used

A membrane system utilizing an amine-containing polymeric membrane with a selective polymer layer and dispersed carbon nanotubes, coated with hydrophilic polymers, is developed to enhance CO2 transport through reactive diffusion, using amino acid salts as mobile carriers and hydrophilically modified carbon nanotubes to improve mechanical strength and selectivity.

Benefits of technology

The membrane system achieves high CO2 flux and selectivity under vacuum conditions, maintaining mechanical integrity and reducing membrane degradation, thereby effectively separating CO2 from N2 in flue gas streams.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611818000016
    Figure 0007611818000016
  • Figure 0007611818000017
    Figure 0007611818000017
  • Figure 0007611818000018
    Figure 0007611818000018
Patent Text Reader

Abstract

[Solution] Membranes, methods of making membranes, and methods of using membranes are described herein. The membranes can include a support layer and a selective polymer layer disposed on the support layer. The selective polymer layer can include a selective polymer matrix and carbon nanotubes dispersed within the selective polymer matrix. The carbon nanotubes can include multi-walled carbon nanotubes coated with a hydrophilic polymer, such as polyvinylpyrrolidone or a copolymer thereof, such as poly(1-vinylpyrrolidone-co-vinyl acetate). The membranes can exhibit selective permeability to gases. Thus, the membranes can be for selectively removing carbon dioxide and / or hydrogen sulfide from hydrogen and / or nitrogen. [Selection diagram] None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority to U.S. Provisional Patent Application No. 62 / 731,790, filed Sep. 14, 2018, which is incorporated by reference in its entirety.

[0002] Statement regarding federally funded research This invention was made with Government support under Grant No. DE-FE0026919 awarded by the U.S. Department of Energy. The Government has certain rights in this invention. [Background technology]

[0003] There are numerous industrial processes that produce gas streams that contain carbon dioxide, hydrogen sulfide, and hydrogen chloride, or that contain carbon dioxide, nitrogen oxides, and sulfur oxides. It is often desirable to remove one or more of these gases from other components of the gas stream, such as hydrogen and nitrogen. Selectively permeable polymeric membranes have been investigated for a variety of gas separation applications, including hydrogen purification and carbon dioxide sequestration. However, there remains a need in the art for membranes, methods of making membranes, and methods of separating gases. The prior art documents relevant to the invention of this application are as follows (including documents cited during the international phase after the international filing date and documents cited when the application entered the national phase in other countries). (Prior art document) (Patent Documents) (Patent Document 1) U.S. Patent Application Publication No. 2010 / 0206811 (Patent Document 2) U.S. Patent Application Publication No. 2013 / 0341570 (Patent Document 3) U.S. Patent Application Publication No. 2018 / 0147513 (Patent Document 4) International Publication No. 2019 / 040445 (Patent Document 5) China Patent Application Publication No. 101821089 (Patent Document 6) Chinese Patent Application Publication No. 103124590 (Patent Document 7) China Patent Application Publication No. 104785122 (Patent Document 8) Chinese Patent No. 107847837 (Patent Document 9) U.S. Patent No. 7,964,020 (Patent Document 10) U.S. Patent No. 9,216,390 (Patent Document 11) U.S. Patent Application Publication No. 2008 / 0168900 (Patent Document 12) U.S. Patent Application Publication No. 2010 / 0206811 (Patent Document 13) U.S. Patent Application Publication No. 2013 / 0341570 (Patent Document 14) U.S. Patent Application Publication No. 2017 / 0056839 (Patent Document 15) U.S. Patent Application Publication No. 2018 / 0147513 (Patent Document 16) International Publication No. 2019 / 040445 (Patent Document 17) U.S. Patent Application Publication No. 2012 / 0080380 (Patent Document 18) U.S. Patent Application Publication No. 2014 / 0370252 (Patent Document 19) U.S. Patent Application Publication No. 2016 / 0263531 (Non-Patent Literature) (Non-patent Document 1) ANSALONI et al.Facilitated transport membranes containing amino-functionalized multi-walled carbon nanotubes for high-pressure CO2 separations, J.Memb.Sci.490(2015)18-28. (Non-Patent Document 2) CHEN et al. New Pebax / zeolite Y composite membranes for CO2 capture from flue gas, J. Membr. Sci. 495 (2015) 415-423. (Non-patent document 3) CHEN et al.High-molecular-weight polyvinylamine / piperazine glycinate membranes for CO2 capture from flue gas, J.Membr.Sci.(2016)376-384 (Non-Patent Document 4) CHEN et al. Amine-containing polymer / zeolite Y composite membranes for CO2 / N2 separation, J. Membr. Sci., 497 (2016) 21-28. (Non-Patent Document 5) CHINESE NATIONAL INTELLECTUAL PROPERTY ADMINISTRATION.Office Action issued for Chinese Application No.201980074095.2,dated March 11,2022. (Non-Patent Document 6) EUROPEAN PATENT OFFICE.Extended European Search report issued for EP Application No.19860928.1,dated May 10,2022. (Non-Patent Document 7) HABIBIANNEJAD et al. Pebax-1657 mixed matrix membrane containing surface modified multi-walled carbon nanotubes for gas separation." RSC advances 6.83 (2016): 79563-79577. (Non-Patent Document 8) HAN et al. Nanotube-reinforced facilitated transport membrane for CO2 / N2 separation with vacuum operation. Journal of Membrane Science 567 (2018): 261-271. (Non-Patent Document 9) HE et al.Energy efficient process for CO2 capture from flue gas with novel fixed-site-carrier membranes,Energy Procedia 63(2014)174-185. (Non-Patent Document 10) HUANG et al. Carbon dioxide capture using a CO2-selective facilitated transport membrane, Ind.Eng.Chem.Res.47(2008)1261-1267. (Non-Patent Document 11) INTERNATIONAL SEARCHING AUTHORITY (ISA / US). International Search Report and Written Opinion issued in PCT Application No. PCT / US2019 / 051308 on November 15, 2019. 8 pages. (Non-Patent Document 12) KIM et al.Separation performance of PVAm composite membrane for CO2 capture at various pH levels, J.Membr.Sci.428(2013)218-224. (Non-Patent Document 13) NEJAD et al. Investigation of carbon nanotubes in mixed matrix membranes for gas separation: a review. ChemBioEng Reviews 3.6 (2016): 276-298. (Non-patent document 14) QIAO et al.Preparation and characterization of small molecular amine modified PVAm membranes for CO2 / H2 separation, J.Membr.Sci.475 (2015) 290-302. (Non-patent document 15) QIAO et al.PVAm-PIP / PS composite membrane with high performance for CO2 / N2 separation, AIChE J.59(2013)215-228. (Non-Patent Document 16) SANDRU et al.Composite hollow fiber membranes for CO2 capture, J.Membr.Sci.346(2010)172-186. (Non-Patent Document 17) WILEN et al. Strategies in optical resolutions. Tetrahedron 33.21 (1977): 2725-2736. (Non-Patent Document 18) WILEN et al. Tables of Resolving Agents and Optical Resolutions p.268 (EL Eliel, Ed., Univ. of Notre Dame Press, Notre Dame, IN 1972) (Non-patent document 19) WU et al. Synthesis and characterization of nanoporous polyethersulfone membrane as support for composite membrane in CO2 separation: From lab to pilot scale, J.Membr.Sci.,510 (2016) 58-71 (Non-patent document 20) YAVE et al. Nanometric thin film membranes manufactured on square meter scale: Ultra-thin films for CO2 capture, Nanotechnology 21 (2010) 395301. (Non-Patent Document 21) YAVE et al. CO2-philic polymer membrane with extremely high separation performance, Macromolecules 43 (2009) 326-333. (Non-patent document 22) ZHAO et al. Multiwalled carbon nanotube mixed matrix membranes containing amines for high pressure CO2 / H2 separation, J.Memb.Sci.459 (2014) 233-243 (Non-Patent Document 23) ZOU et al. CO2-selective polymeric membranes containing amines in crosslinked poly(vinyl alcohol), J.Membr.Sci.286 (2006) 310-321. Summary of the Invention

[0004] Membranes for gas separation are disclosed, including amine-containing polymeric membranes that selectively remove CO2 from CO2 / N2 mixtures, e.g., flue gas from coal or natural gas. Significant CO2 flux and CO2 / N2 selectivity are achieved by reactive diffusion of CO2 through a support (e.g., an amine support). Amino polymers can be used to form a polymer matrix in the selective layer of the membrane, which acts as a fixed site support. Amino acid salts synthesized by reacting bases, e.g., piperazine, and 2-(1-piperazinyl)ethylamine, with amino acids, e.g., glycine, sarcosine, and 2-aminoisobutyric acid, can be blended with amino polymers as transfer carriers. As shown by the examples, these amino acid salts can function as effective transfer carriers to enhance the permeation of CO2 through ultrathin membranes at operating temperatures of 57-87°C.

[0005] For practical separation of CO2 from flue gas, a sufficient transmembrane pressure difference is often used to provide a driving force for CO2 permeation. For this purpose, a vacuum is typically pulled on the downstream side. For polymeric membrane materials, suitable mechanical properties are required to maintain the vacuum suction. Methods are also described for hydrophilically modifying carbon nanotubes (e.g., multi-walled carbon nanotubes, MWNTs) and dispersing them in polymeric selective layers as inorganic reinforcing fillers. As demonstrated in the examples, both polymer coatings with polyvinylpyrrolidone and poly(1-vinylpyrrolidone-co-vinyl acetate) allow for the effective elimination of the hydrophobic surface of MWNTs, which greatly improves the dispersion of MWNTs in amine-containing selective layers. The MWNT network structure reduces the penetration of the selective layer into the nanoporous support under vacuum. [Brief description of the drawings]

[0006] [Figure 1] The chemical structure of PZEA-Sar is shown. [Diagram 2] 1 shows a gas permeation unit used for gas permeation measurements that allows for scavenging and vacuum operation. [Figure 3A] 3A and 3B show SEM images of the membrane cross section of the membrane prepared in Example 1A. FIG. 3A and 3B are cross sections of the membrane without MWNTs before and after vacuum testing, respectively. [Figure 3B] 3A and 3B show SEM images of the membrane cross section of the membrane prepared in Example 1A. FIG. 3A and 3B are cross sections of the membrane without MWNTs before and after vacuum testing, respectively. [Figure 4A] 4A and 4B show SEM images of the membrane cross-sections of the membrane with PVP7-co-Vac3 / MWNT before and after vacuum testing, respectively. [Figure 4B] 4A and 4B show SEM images of the membrane cross-sections of the membrane with PVP7-co-Vac3 / MWNT before and after vacuum testing, respectively. [Figure 5A]Figure 5 shows the effect of feed pressure on CO2 permeability and CO2 / N2 selectivity at 57°C with a vacuum of 0.2 atm on the permeate side. Figure 5A shows these effects under a constant feed CO2 concentration, and Figure 5B shows these effects under a constant feed CO2 partial pressure of 0.166 atm. [Figure 5B] Figure 5 shows the effect of feed pressure on CO2 permeability and CO2 / N2 selectivity at 57°C with a vacuum of 0.2 atm on the permeate side. Figure 5A shows these effects under a constant feed CO2 concentration, and Figure 5B shows these effects under a constant feed CO2 partial pressure of 0.166 atm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Disclosed herein is a membrane that includes a support layer and a selective polymer layer disposed (e.g., coated) on the support layer. The selective polymer layer can include a selective polymer matrix and carbon nanotubes dispersed within the selective polymer matrix. The carbon nanotubes can be coated with a hydrophilic polymer.

[0008] Methods for making these membranes and methods for using these membranes are also provided.

[0009] definition As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "pharmaceutical carrier" includes mixtures of two or more such carriers, and the like.

[0010] Ranges can be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes from one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, it will be understood that by using the antecedent "about," the particular value forms another embodiment. It will be further understood that the endpoints of each range are significant both in relation to the other endpoint, and independently of the other endpoint. It will also be understood that there are a number of values ​​disclosed herein, and that each value is herein disclosed as "about" that particular value, in addition to the value itself. For example, if the value "10" is disclosed, "about 10" is also disclosed. It is also understood that when a value is disclosed, "less than or equal to," "greater than or equal to," and possible ranges between the values ​​are also disclosed, as would be properly understood by one of ordinary skill in the art. For example, if the value "10" is disclosed, "less than or equal to 10" as well as "greater than or equal to 10" are also disclosed. It is also understood that throughout the application, data is provided in many different formats, and that the data represents endpoints and starting points, ranges of any combination of data points. For example, if a specific data point "10" and a specific data point 15 are disclosed, it is understood that greater than, greater than, less than, less than, and equal to 10 and 15, as well as 10 to 15, are considered to be disclosed. It is also understood that each unit between two specific units is also disclosed. For example, if 10 and 15 are disclosed, then 11, 12, 13, and 14 are also disclosed.

[0011] Throughout this specification and the claims that follow, reference will be made to a number of terms that shall be defined to have the following meanings.

[0012] "Optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and is meant to include instances in which the event or circumstance occurs and instances in which the circumstance does not occur.

[0013] The term "n-membered," where n is an integer, typically describes the number of ring-forming atoms of a moiety, where the number of ring-forming atoms is n. For example, piperidinyl is an example of a 6-membered heterocycloalkyl ring, pyrazolyl is an example of a 5-membered heteroaryl ring, pyridyl is an example of a 6-membered heteroaryl ring, and 1,2,3,4-tetrahydro-naphthalene is an example of a 10-membered cycloalkyl group.

[0014] As used herein, the phrase "optionally substituted" means unsubstituted or substituted. As used herein, the term "substituted" means that a hydrogen atom has been removed and replaced with a substituent. It is understood that substitution at a given atom is limited by the valence of the atom.

[0015] Throughout the definition, "C n~m " denotes a range inclusive of the endpoints, where n and m are integers and indicate the number of carbons. Examples include C 1~4 , C 1~6 etc.

[0016] As used herein, "C n~m The term "alkyl", employed alone or in combination with other terms, refers to a saturated hydrocarbon group having n to m carbons, which may be linear or branched. Examples of alkyl moieties include, but are not limited to, chemical groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, isobutyl, sec-butyl, higher homologs such as 2-methyl-1-butyl, n-pentyl, 3-pentyl, n-hexyl, 1,2,2-trimethylpropyl, and the like. In some embodiments, an alkyl group contains 1 to 6 carbon atoms, 1 to 4 carbon atoms, 1 to 3 carbon atoms, or 1 to 2 carbon atoms.

[0017] As used herein, "C n~m"Alkenyl" refers to an alkyl group having one or more double carbon-carbon bonds and having n to m carbons. Examples of alkenyl groups include, but are not limited to, ethenyl, n-propenyl, isopropenyl, n-butenyl, sec-butenyl, and the like. In some embodiments, the alkenyl moiety contains 2 to 6, 2 to 4, or 2 to 3 carbon atoms.

[0018] As used herein, "C n~m "Alkynyl" refers to an alkyl group having one or more triple carbon-carbon bonds and having n to m carbons. Examples of alkynyl groups include, but are not limited to, ethynyl, propyn-1-yl, propyn-2-yl, and the like. In some embodiments, the alkynyl moiety contains 2 to 6, 2 to 4, or 2 to 3 carbon atoms.

[0019] As used herein, "C n~m The term "alkylene", employed alone or in combination with other terms, refers to a divalent alkyl linking group having n to m carbons. Examples of alkylene groups include, but are not limited to, ethane-1,2-diyl, propane-1,3-diyl, propane-1,2-diyl, butane-1,4-diyl, butane-1,3-diyl, butane-1,2-diyl, 2-methyl-propane-1,3-diyl, and the like. In some embodiments, the alkylene moiety contains 2 to 6, 2 to 4, 2 to 3, 1 to 6, 1 to 4, or 1 to 2 carbon atoms.

[0020] As used herein, "C n~m The term "alkoxy," employed alone or in combination with other terms, refers to a group of formula -O-alkyl, where the alkyl group has n to m carbons. Examples of alkoxy groups include methoxy, ethoxy, propoxy (e.g., n-propoxy and isopropoxy), tert-butoxy, and the like. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0021] As used herein, "Cn~m The term "alkylamino" refers to a group of formula -NH(alkyl), where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0022] As used herein, "C n~m The term "alkoxycarbonyl" refers to a group of formula -C(O)O-alkyl, where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0023] As used herein, "C n~m The term "alkylcarbonyl" refers to a group of formula -C(O)-alkyl, where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0024] As used herein, "C n~m The term "alkylcarbonylamino" refers to a group of formula -NHC(O)-alkyl, where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0025] As used herein, "C n~m The term "alkylsulfonylamino" refers to a group of formula -NHS(O)2-alkyl, where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0026] As used herein, the term "aminosulfonyl" refers to a group of formula -S(O)2NH2.

[0027] As used herein, "C n~mThe term "alkylaminosulfonyl" refers to a group of formula -S(O)NH(alkyl), where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0028] As used herein, "di(C n~m The term "aminosulfonyl" refers to a group of formula -S(O)N(alkyl) where each alkyl group independently has n to m carbon atoms. In some embodiments, each alkyl group independently has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0029] As used herein, the term "aminosulfonylamino" refers to a group of formula -NHS(O)2NH2.

[0030] As used herein, "C n~m The term "alkylaminosulfonylamino" refers to a group of formula -NHS(O)NH(alkyl), where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0031] As used herein, "di(C n~m The term "NHS(O)N(alkyl)aminosulfonylamino" refers to a group of formula -NHS(O)N(alkyl) where each alkyl group independently has n to m carbon atoms. In some embodiments, each alkyl group independently has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0032] As used herein, the term "aminocarbonylamino," employed alone or in combination with other terms, refers to a group of formula -NHC(O)NH2.

[0033] As used herein, "C n~mThe term "alkylaminocarbonylamino" refers to a group of formula -NHC(O)NH(alkyl), where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0034] As used herein, "di(C n~m The term "NHC(O)N(alkyl)aminocarbonylamino" refers to a group of formula -NHC(O)N(alkyl)2, where each alkyl group independently has n to m carbon atoms. In some embodiments, each alkyl group independently has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0035] As used herein, "C n~m The term "alkylcarbamyl" refers to a group of formula -C(O)-NH(alkyl), where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0036] As used herein, the term "thio" refers to a group of formula --SH.

[0037] As used herein, "C n~m The term "alkylsulfinyl" refers to a group of formula -S(O)-alkyl, where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0038] As used herein, "C n~m The term "alkylsulfonyl" refers to a group of formula -S(O)2-alkyl, where the alkyl group has n to m carbon atoms. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0039] As used herein, the term "amino" refers to a group of formula -NH2.

[0040] As used herein, the term "aryl," employed alone or in combination with other terms, refers to an aromatic hydrocarbon group that can be monocyclic or polycyclic (e.g., having 2, 3, or 4 fused rings). n~m The term "aryl" refers to an aryl group having n to m ring carbon atoms. Examples of aryl groups include phenyl, naphthyl, anthracenyl, phenanthrenyl, indanyl, indenyl, and the like. In some embodiments, an aryl group has from 6 to about 20 carbon atoms, from 6 to about 15 carbon atoms, or from 6 to about 10 carbon atoms. In some embodiments, an aryl group is a substituted or unsubstituted phenyl.

[0041] As used herein, the term "carbamyl" refers to a group of formula -C(O)NH2.

[0042] As used herein, the term "carbonyl" employed alone or in combination with other terms, refers to a -C(=O)- group, which may also be written as C(O).

[0043] As used herein, "di(C n~m The term "-N(alkyl)amino" refers to a group of formula -N(alkyl)2, where the two alkyl groups each independently have n to m carbon atoms. In some embodiments, each alkyl group independently has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0044] As used herein, "di(C n~m The term "-alkyl)carbamyl" refers to a group of formula -C(O)N(alkyl), where the two alkyl groups each independently have n to m carbon atoms. In some embodiments, each alkyl group independently has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0045] As used herein, the term "halo" refers to F, Cl, Br, or I. In some embodiments, halo is F, Cl, or Br. In some embodiments, halo is F or Cl.

[0046] As used herein, "C n~m "Haloalkoxy" refers to a group of formula -O-haloalkyl, where the haloalkyl group has n to m carbon atoms. An example of a haloalkoxy group is OCF3. In some embodiments, the haloalkoxy group is exclusively fluorinated. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0047] As used herein, "C n~m The term "haloalkoxy", employed alone or in combination with other terms, refers to an alkyl group having from one halogen atom to 2s+1 halogen atoms, which may be the same or different, where "s" is the number of carbon atoms in the alkyl group, and the alkyl group has n to m carbon atoms. In some embodiments, the haloalkyl group is exclusively fluorinated. In some embodiments, the alkyl group has 1 to 6, 1 to 4, or 1 to 3 carbon atoms.

[0048] As used herein, "cycloalkyl" refers to a non-aromatic cyclic hydrocarbon, including cyclized alkyl and / or alkenyl groups. Cycloalkyl groups can include monocyclic or polycyclic groups (e.g., having 2, 3, or 4 fused rings), and spirocycles. Cycloalkyl groups can have 3, 4, 5, 6, 7, 8, 9, or 10 ring-forming carbons (C 3~10). The ring-forming carbon atoms of a cycloalkyl group may be optionally substituted by oxo or sulfido (e.g., C(O) or C(S)). Cycloalkyl groups also include cycloalkylidenes. Examples of cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclopentenyl, cyclohexenyl, cyclohexadienyl, cycloheptatrienyl, norbornyl, norpinyl, norcarnyl, and the like. In some embodiments, a cycloalkyl is cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cyclopentyl, or adamantyl. In some embodiments, a cycloalkyl has from 6 to 10 ring-forming carbon atoms. In some embodiments, a cycloalkyl is adamantyl. The definition of cycloalkyl also includes moieties having one or more aromatic rings fused (i.e., having a bond in common) to the cycloalkyl ring (e.g., benzo or thienyl derivatives of cyclopentane, cyclohexane, and the like). Cycloalkyl groups containing fused aromatic rings may be attached through any ring-forming atom, including a ring-forming atom of the fused aromatic ring.

[0049] As used herein, "heteroaryl" refers to a monocyclic or polycyclic aromatic heterocycle having at least one heteroatom ring member selected from sulfur, oxygen, and nitrogen. In some embodiments, the heteroaryl ring has 1, 2, 3, or 4 heteroatom ring members independently selected from nitrogen, sulfur, and oxygen. In some embodiments, any ring-forming N in the heteroaryl moiety can be an N-oxide. In some embodiments, the heteroaryl has 5-10 ring atoms and 1, 2, 3, or 4 heteroatom ring members independently selected from nitrogen, sulfur, and oxygen. In some embodiments, the heteroaryl has 5-6 ring atoms and 1 or 2 heteroatom ring members independently selected from nitrogen, sulfur, and oxygen. In some embodiments, the heteroaryl is a 5- or 6-membered heteroaryl ring. A 5-membered heteroaryl ring is a heteroaryl having a ring with 5 ring atoms, where one or more (e.g., 1, 2, or 3) ring atoms are independently selected from N, O, and S. Exemplary 5-membered heteroaryls are thienyl, furyl, pyrrolyl, imidazolyl, thiazolyl, oxazolyl, pyrazolyl, isothiazolyl, isoxazolyl, 1,2,3-triazolyl, tetrazolyl, 1,2,3-thiadiazolyl, 1,2,3-oxadiazolyl, 1,2,4-triazolyl, 1,2,4-thiadiazolyl, 1,2,4-oxadiazolyl, 1,3,4-triazolyl, 1,3,4-thiadiazolyl, and 1,3,4-oxadiazolyl. A 6-membered heteroaryl ring is a heteroaryl having a ring with 6 ring atoms, one or more (e.g., 1, 2, or 3) ring atoms are independently selected from N, O, and S. Exemplary 6-membered heteroaryls are pyridyl, pyrazinyl, pyrimidinyl, triazinyl, and pyridazinyl.

[0050] As used herein, "heterocycloalkyl" refers to a non-aromatic monocyclic or polycyclic heterocycle having one or more ring-forming heteroatoms selected from O, N, or S. Heterocycloalkyl includes monocyclic 4-, 5-, 6-, and 7-membered heterocycloalkyl groups. Heterocycloalkyl groups can also include spirocycles. Examples of heterocycloalkyl groups include pyrrolidin-2-one, 1,3-isoxazolidin-2-one, pyranyl, tetrahydrofuran, oxetanyl, azetidinyl, morpholino, thiomorpholino, piperazinyl, tetrahydrofuranyl, tetrahydrothienyl, piperidinyl, pyrrolidinyl, isoxazolidinyl, isothiazolidinyl, pyrazolidinyl, oxazolidinyl, thiazolidinyl, imidazolidinyl, azepanyl, benzazapene, and the like. The ring-forming carbon atoms and heteroatoms of a heterocycloalkyl group may be optionally substituted with oxo or sulfido (e.g., C(O), S(O), C(S), or S(O)2, etc.). A heterocycloalkyl group may be bonded through a ring-forming carbon atom or a ring-forming heteroatom. In some embodiments, a heterocycloalkyl group contains 0-3 double bonds. In some embodiments, a heterocycloalkyl group contains 0-2 double bonds. Also included in the definition of heterocycloalkyl are moieties that have one or more aromatic rings fused (i.e., having a common bond) to a cycloalkyl ring (e.g., benzo or thienyl derivatives of piperidine, morpholine, azepine, etc.). Heterocycloalkyl groups that contain fused aromatic rings may be bonded through any ring-forming atom, including a ring-forming atom of the fused aromatic ring. In some embodiments, a heterocycloalkyl has 4-10, 4-7, or 4-6 ring atoms and 1 or 2 heteroatoms independently selected from nitrogen, oxygen, or sulfur, and has one or more oxidized ring members.

[0051] In certain places, the definitions or embodiments refer to certain rings (e.g., azetidine ring, pyridine ring, etc.). Unless otherwise indicated, these rings may be bonded to any ring member, provided that the valence of the atom is not exceeded. For example, the azetidine ring may be bonded to any position of the ring, while the pyridin-3-yl ring is bonded to the 3-position.

[0052] The term "compound" as used herein is meant to include all stereoisomers, geometric isomers, tautomers, and isotopes of the structures depicted. Compounds identified herein by name or structure as one particular tautomeric form are intended to include other tautomeric forms unless otherwise specified.

[0053] The compounds provided herein also include tautomeric forms. Tautomeric forms result from the exchange of a single bond with an adjacent double bond with the concomitant migration of a proton. Tautomeric forms include prototropic tautomers, which are isomeric protonation states with the same empirical formula and total charge. Examples of prototropic tautomers include ketone-enol pairs, amide-imidic acid pairs, lactam-lactim pairs, enamine-imine pairs, and cyclic forms in which protons can occupy more than one position of a heterocyclic ring system, such as 1H- and 3H-imidazole, 1H-, 2H-, and 4H-1,2,4-triazole, 1H- and 2H-isoindole, and 1H- and 2H-pyrazole. Tautomeric forms can be in equilibrium or can be sterically fixed in one form by appropriate substitution.

[0054] In some embodiments, the compounds described herein may contain one or more asymmetric centers and thus occur as racemates and racemic mixtures, enantiomerically enriched mixtures, single enantiomers, individual diastereoisomers and diastereoisomeric mixtures (e.g., (R)- and (S)-enantiomers, diastereoisomers, (D)-isomers, (L)-isomers, (+) (dextrorotatory) forms, (-) (levorotatory) forms, racemic mixtures thereof, and other mixtures thereof). Additional asymmetric carbon atoms may be present in substituents such as alkyl groups. All such isomeric forms of these compounds, as well as mixtures thereof, are expressly included herein. The compounds described herein may also contain or further contain bonds in which bond rotation is restricted about a particular bond (e.g., restrictions due to the presence of a ring or double bond (e.g., carbon-carbon bond, carbon-nitrogen bond such as an amide group)). Thus, all cis / trans and E / Z isomers, as well as rotational isomers, are expressly included herein. Unless otherwise stated or indicated, the chemical name of a compound encompasses the mixture of all possible stereochemically isomeric forms of that compound.

[0055] Optical isomers can be obtained in pure form by standard procedures known to those skilled in the art, including, but not limited to, formation of diastereoisomeric salts, kinetic resolution, and asymmetric synthesis.See, for example, Jacques, et al., Enantiomers, Racemates and Resolutions (Wiley Interscience, New York, 1981); Wilen, SH, et al., Tetrahedron 33:2725 (1977); Eliel, EL, Stereochemistry of Carbon Compounds (McGraw-Hill, NY, 1962); Wilen, SH, Tables of Resolving Agents and Optical Resolutions p.268 (EL Eliel, Ed., Univ. of Notre Dame Press, Notre Dame, IN 1972).Each of these is incorporated herein by reference in its entirety. It is also understood that the compounds described herein include all possible positional isomers, and mixtures thereof, which can be obtained in pure form by standard separation procedures known to those skilled in the art, including, but not limited to, column chromatography, thin layer chromatography, and high performance liquid chromatography.

[0056] support layer The support layer may be formed from any suitable material. The material used to form the support layer may be selected based on the end use application of the membrane. In some embodiments, the support layer may include a gas-permeable polymer. The gas-permeable polymer may be a crosslinked polymer, a phase-separated polymer, a porous condensation polymer, or a blend thereof. Examples of suitable gas-permeable polymers include polyamides, polyimides, polypyrrolones, polyesters, sulfone-based polymers, nitrile-based polymers, polymeric organosilicones, fluorinated polymers, polyolefins, copolymers thereof, or blends thereof. Specific examples of polymers that may be present in the support layer include polydimethylsiloxane, polydiethylsiloxane, polydi-iso-propylsiloxane, polydiphenylsiloxane, polyethersulfone, polyphenylsulfone, polysulfone, polyacrylonitrile, polyvinylidene fluoride, polyamide, polyimide, polyetherimide, polyetheretherketone, polyphenylene oxide, polybenzimidazole, polypropylene, polyethylene, partially fluorinated, perfluorinated, or sulfonated derivatives thereof, copolymers thereof, or blends thereof. In some embodiments, the gas-permeable polymer may be polysulfone or polyethersulfone. Optionally, the support layer may contain inorganic particles to increase mechanical strength without changing the permeability of the support layer.

[0057] In certain embodiments, the support layer may include a gas-permeable polymer disposed on a base. The base may be any configuration configured to facilitate the formation of a membrane suitable for use in a particular application. For example, the base may be a flat disk, a tube, a spiral wound, or a hollow fiber base. The base may be formed from any suitable material. In some embodiments, the layer may include a fibrous material. The fibrous material in the base may be a mesh (e.g., a metal or polymer mesh), a woven or nonwoven fabric, glass, fiberglass, resin, a screen (e.g., a metal or polymer screen). In certain embodiments, the base may include a nonwoven fabric (e.g., a nonwoven fabric including fibers formed from polyester).

[0058] Selective polymer layer The selective polymer layer may include a selective polymer matrix and carbon nanotubes dispersed within the selective polymer matrix. The carbon nanotubes may be coated with a hydrophilic polymer.

[0059] The selective polymer matrix may include a hydrophilic polymer, an amine-containing polymer, or a combination thereof. Optionally, the selective polymer matrix may further include an additional component, such as an amine-based transfer carrier (e.g., a low molecular weight amino compound) dispersed within the polymer matrix. By way of example, in some embodiments, the selective polymer layer may include an amine-containing polymer (e.g., polyvinylamine), a hydrophilic polymer (e.g., polyvinyl alcohol), and an amine-based transfer carrier (e.g., PZEA-Sar, PZEA-AIBA, HEP, or a combination thereof).

[0060] In some cases, the selective polymer layer can be a polymer matrix through which gas permeates via diffusion or facilitated diffusion. The selective polymer layer can include a polymer matrix having a CO2:N2 selectivity of at least 10 at 57°C and 1 atm feed pressure. For example, the polymer matrix can have a CO2:N2 selectivity of at least 25 (e.g., at least 50, at least 75, at least 100, at least 125, at least 150, at least 175, at least 200, at least 225, at least 250, at least 275, at least 300, at least 325, at least 350, at least 375, at least 400, at least 425, at least 450, or at least 475) at 57°C and 1 atm feed pressure. In some embodiments, the polymer matrix may have a CO2:N2 selectivity of 500 or less (e.g., 475 or less, 450 or less, 425 or less, 400 or less, 375 or less, 350 or less, 325 or less, 300 or less, 275 or less, 250 or less, 225 or less, 200 or less, 175 or less, 150 or less, 125 or less, 100 or less, 75 or less, 50 or less, or 25 or less) at 57°C and 1 atmosphere of feed pressure.

[0061] In certain examples, the selective polymer layer may comprise a polymer matrix having a CO2:N2 selectivity ranging from any of the minimum values ​​described above to any of the maximum values ​​described above. For example, in certain embodiments, the selective polymer layer may comprise a polymer matrix having a CO2:N2 selectivity of 10-500 at 57° C. and 1 atm feed pressure (e.g., 10-400 at 57° C. and 1 atm feed pressure, 75-400 at 57° C. and 1 atm feed pressure, 100-400 at 57° C. and 1 atm feed pressure, 10-350 at 57° C. and 1 atm feed pressure, 75-350 at 57° C. and 1 atm feed pressure, 100-350 at 57° C. and 1 atm feed pressure, 10-250 at 57° C. and 1 atm feed pressure, 75-250 at 57° C. and 1 atm feed pressure, or 100-250 at 57° C. and 1 atm feed pressure). The CO2:N2 selectivity of a selective polymer can be measured using standard methods for measuring gas permeability known in the art, such as those described in the embodiments below.

[0062] If desired, the selective polymer layer may be surface modified, for example by chemical grafting, blending, or coating, to improve the performance of the selective polymer layer. For example, a hydrophobic component may be added to the selective polymer layer to change the properties of the selective polymer layer in a manner that promotes better fluid selectivity.

[0063] The total thickness of each layer in the membrane can be selected so that the structure is mechanically robust, but not so thick as to impair permeability. In some embodiments, the selective polymer layer can have a thickness of 50 nanometers to 5 micrometers (e.g., 50 nm to 2 micrometers, or 100 nanometers to 750 micrometers, or 250 nanometers to 500 micrometers). In some embodiments, the support layer can have a thickness of 1 micrometer to 500 micrometers (e.g., 50 to 250 micrometers). In some cases, the membranes disclosed herein can have a thickness of 5 micrometers to 500 micrometers.

[0064] Selective Polymer Matrix The selective polymer matrix may comprise a hydrophilic polymer, an amine-containing polymer, or a combination thereof. In certain embodiments, the selective polymer matrix may comprise a hydrophilic polymer. In certain embodiments, the selective polymer matrix may comprise an amine-containing polymer. In certain embodiments, the selective polymer matrix may comprise a hydrophilic polymer and an amine-containing polymer.

[0065] When present, the hydrophilic polymer may comprise any suitable hydrophilic polymer. Examples of hydrophilic polymers suitable for use in the selective polymer layer may include polyvinyl alcohol, polyvinyl acetate, polyethylene oxide, polyvinylpyrrolidone, polyacrylamine, polyamines such as polyallylamine, polyvinylamine, or polyethyleneimine, copolymers thereof, and blends thereof. In some embodiments, the hydrophilic polymer comprises polyvinyl alcohol.

[0066] When present, the hydrophilic polymer may have any suitable molecular weight. For example, the hydrophilic polymer may have a weight average molecular weight of 15,000 Da to 2,000,000 Da (e.g., 50,000 Da to 200,000 Da). In some embodiments, the hydrophilic polymer may include polyvinyl alcohol having a weight average molecular weight of 50,000 Da to 150,000 Da. In other embodiments, the hydrophilic polymer may be a high molecular weight hydrophilic polymer. For example, the hydrophilic polymer may have a weight average molecular weight of at least 500,000 Da (e.g., at least 700,000 Da, or at least 1,000,000 Da).

[0067] The selective polymer matrix can include any suitable amount of hydrophilic polymer, for example, in some cases, the selective polymer matrix can include 10% to 90% by weight (e.g., 10% to 50% by weight, or 10% to 30% by weight) of hydrophilic polymer, based on the total weight of the components used to form the selective polymer matrix.

[0068] The selective polymer matrix may also include an amine-containing polymer (also referred to herein as an "immobilizing support"). When present, the amine-containing polymer may have any suitable molecular weight. For example, the amine-containing polymer may have a weight average molecular weight of 5,000 Da to 5,000,000 Da, or 50,000 Da to 2,000,000 Da.

[0069] Suitable examples of amine-containing polymers include, but are not limited to, polyvinylamine, polyallylamine, polyethyleneimine, poly-N-isopropylallylamine, poly-N-tert-butylallylamine, poly-N-1,2-dimethylpropylallylamine, poly-N-methylallylamine, poly-N,N-dimethylallylamine, poly-2-vinylpiperidine, poly-4-vinylpiperidine, polyaminostyrene, chitosan, copolymers, and blends thereof. In some embodiments, the amine-containing polymer may include polyvinylamine (e.g., polyvinylamine having a weight average molecular weight of 50,000 Da to 2,000,000 Da).

[0070] The selective polymer matrix can include any suitable amount of amine-containing polymer, for example, in some cases, the selective polymer matrix can include 10% to 90% (e.g., 10% to 50% or 10% to 30% by weight) of amine-containing polymer, based on the total weight of the components used to form the selective polymer matrix.

[0071] Amine-containing mobile carriers Suitable amine-containing transfer carriers may include small molecules that contain one or more primary amine moieties and / or one or more secondary amine moieties, such as amino acid salts, which may function as "transfer carriers" for CO2 within the polymer matrix.

[0072] In some embodiments, the amine-containing transfer carrier can have a molecular weight of 1,000 Da or less (e.g., 800 Da or less, 500 Da or less, 300 Da or less, or 250 Da or less). In some embodiments, the amine-containing transfer carrier can be non-volatile at the temperature at which the membrane is stored or used. For example, the amine-containing transfer carrier can include a salt of a primary amine or a salt of a secondary amine.

[0073] In some cases, the amine-containing transfer carrier may include an amino acid salt. The amino acid salt may be the salt of any suitable amino acid. The amino acid salt may be derived from, for example, glycine, arginine, lysine, histidine, 6-aminohexanoic acid, proline, sarcosine, methionine, or taurine. In some cases, the amino acid salt may include the salt of a compound defined by the following formula: [ka] wherein, independently for each occurrence of an amino acid, each of R1, R2, R3, and R4 is selected from one of the following: [ka] Or R1 and R3, together with the atoms to which they are attached, form a 5-membered heterocycle defined by the following structure when n is 1, or a 6-membered heterocycle defined by the following structure when n is 2: [ka]

[0074] Poly(amino acids), such as polyarginine, polylysine, polynithine, or polyhistidine, can also be used to prepare the amino acid salts.

[0075] In other embodiments, the amine-containing transfer support may be defined by the following formula: [ka]

[0076] In the formula, R1, R2, R3, and R4 are hydrogen or a hydrocarbon group having 1 to 4 carbon atoms, n is an integer ranging from 0 to 4, and A m+ is a cation having a valence of 1 to 3. m+ ) can be an amine cation having the formula: [ka]

[0077] In the formula, R5 and R6 are hydrogen or a hydrocarbon group having 1 to 4 carbon atoms, R7 is hydrogen or a hydrocarbon group having 1 to 4 carbon atoms, or an alkylamine of 2 to 6 carbon atoms and 1 to 4 nitrogen atoms, y is an integer ranging from 1 to 4, and m is an integer equal to the valence of the cation. m+ is a metal cation selected from Groups Ia, IIa, and IIIa of the Periodic Table of Elements, or transition metals. For example, A m+ may include lithium, aluminum, or iron.

[0078] Other suitable amine-containing transfer carriers include aminoisobutyric acid potassium salt, aminoisobutyric acid lithium salt, aminoisobutyric acid piperazine salt, glycine potassium salt, glycine lithium salt, glycine piperazine salt, dimethylglycine potassium salt, dimethylglycine lithium salt, dimethylglycine piperazine salt, piperazine-2-carboxylic acid potassium salt, piperidine-2-carboxylic acid lithium salt, piperazine-2-carboxylic acid-piperazine salt, piperazine-4-carboxylic acid potassium salt, piperidine-4-carboxylic acid lithium salt, piperazine-4-carboxylic acid-piperazine salt, piperazine-3-carboxylic acid potassium salt, piperidine-3-carboxylic acid lithium salt, piperazine-3-carboxylic acid-piperazine salt, and blends thereof.

[0079] Other Ingredients In some embodiments, the selective polymer matrix may further include a crosslinking agent. Suitable crosslinking agents for use in the polymer matrix may include, but are not limited to, formaldehyde, glutaraldehyde, maleic anhydride, glyoxal, divinyl sulfone, toluene diisocyanate, trimethylol melamine, terephthalate aldehyde, epichlorohydrin, vinyl acrylate, and combinations thereof. In some embodiments, the crosslinking agent may include formaldehyde, glutaraldehyde, or maleic anhydride. The selective polymer matrix may include any suitable amount of crosslinking agent. For example, the polymer matrix may include 1 to 40 percent of the crosslinking agent by weight of the polymer matrix.

[0080] The selective polymer matrix may further include a base. The base may act as a catalyst to catalyze the crosslinking of the polymer matrix (e.g., crosslinking of a hydrophilic polymer with an amine-containing polymer). In some embodiments, the base may remain in the polymer matrix and may form part of the polymer matrix. Examples of suitable bases include potassium hydroxide, sodium hydroxide, lithium hydroxide, triethylamine, N,N-dimethylaminopyridine, hexamethyltriethylenetetraamine, potassium carbonate, sodium carbonate, lithium carbonate, and combinations thereof. In some embodiments, the base may include potassium hydroxide. The polymer matrix may include any suitable amount of base. For example, the polymer matrix may include 1 to 40 percent of the base by weight of the polymer matrix.

[0081] Carbon Nanotubes The selective polymer layer may include carbon nanotubes dispersed within a selective polymer matrix. The carbon nanotubes may be coated with a hydrophilic polymer.

[0082] Any suitable carbon nanotubes (prepared by any suitable method or obtained from a commercial source) may be used. The carbon nanotubes may include single-walled carbon nanotubes, multi-walled carbon nanotubes, or a combination thereof.

[0083] In some cases, the carbon nanotubes can have an average diameter of at least 10 nm (e.g., at least 20 nm, at least 30 nm, or at least 40 nm). In some cases, the carbon nanotubes can have an average diameter of 50 nm or less (e.g., 40 nm or less, 30 nm or less, or 20 nm or less). In certain embodiments, the carbon nanotubes can have an average diameter ranging from any of the minimum values ​​listed above to any of the maximum values ​​listed above. For example, the carbon nanotubes can have an average diameter of 10 nm to 50 nm (e.g., 10 nm to 30 nm, or 20 nm to 50 nm).

[0084] In some cases, the carbon nanotubes can have an average length of at least 50 nm (e.g., at least 100 nm, at least 200 nm, at least 300 nm, at least 400 nm, at least 500 nm, at least 600 nm, at least 700 nm, at least 800 nm, at least 900 nm, at least 1 μm, at least 5 μm, at least 10 μm, or at least 15 μm). In some cases, the carbon nanotubes can have an average length of 20 μm or less (e.g., 15 μm or less, 10 μm or less, 5 μm or less, 1 μm or less, 900 nm or less, 800 nm or less, 700 nm or less, 600 nm or less, 500 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, or 100 nm or less).

[0085] In certain embodiments, the carbon nanotubes can have an average length ranging from any of the minimum values ​​above to any of the maximum values ​​above. For example, the carbon nanotubes can have an average length of 50 nm to 20 μm (e.g., 200 nm to 20 μm, or 500 nm to 10 μm).

[0086] In some cases, the carbon nanotubes may include non-functionalized carbon nanotubes. In other embodiments, the carbon nanotubes may include sidewall-functionalized carbon nanotubes. Sidewall-functionalized carbon nanotubes are well known in the art. Suitable sidewall-functionalized carbon nanotubes may be prepared from non-functionalized carbon nanotubes, for example, by creating defects on the sidewalls by strong acid oxidation. The defects created by the oxidizing agent may then be converted to more stable hydroxyl and carboxylic acid groups. The hydroxyl and carboxylic acid groups on the acid-treated carbon nanotubes may then be bonded to other functional group-containing reagents (e.g., amine-containing reagents), thereby introducing pendant functional groups (e.g., amino groups) on the sidewalls of the carbon nanotubes. In some embodiments, the carbon nanotubes may include hydroxy-functionalized carbon nanotubes, carboxy-functionalized carbon nanotubes, amine-functionalized carbon nanotubes, or combinations thereof.

[0087] In some embodiments, the selective polymer layer may comprise at least 0.5 wt% (e.g., at least 1 wt%, at least 1.5 wt%, at least 2 wt%, at least 2.5 wt%, at least 3 wt%, at least 3.5 wt%, at least 4 wt%, or at least 4.5 wt%) carbon nanotubes based on the total dry weight of the selective polymer layer. In some embodiments, the selective polymer layer may comprise 5 wt% or less (e.g., 4.5 wt% or less, 4 wt% or less, 3.5 wt% or less, 3 wt% or less, 2.5 wt% or less, 2 wt% or less, 1.5 wt% or less, or 1 wt% or less) carbon nanotubes based on the total dry weight of the selective polymer layer.

[0088] The selective polymer layer may include an amount of carbon nanotubes ranging from any of the minimum values ​​described above to any of the maximum values ​​described above. For example, the selective polymer layer may include 0.5% to 5% (e.g., 1% to 3%) by weight of carbon nanotubes, based on the total dry weight of the selective polymer layer.

[0089] The hydrophilic polymer may include any suitable hydrophilic polymer. Examples of hydrophilic polymers suitable for use in the selective polymer layer may include polyvinyl alcohol, polyvinyl acetate, polyethylene oxide, polyvinylpyrrolidone, polyacrylamine, polyamines, such as polyallylamine, polyvinylamine, or polyethyleneimine, copolymers thereof, and blends thereof. In some embodiments, the hydrophilic polymer may have a weight average molecular weight of 15,000 Da to 2,000,000 Da (e.g., 50,000 Da to 200,000 Da). In some embodiments, the hydrophilic polymer may include polyvinylpyrrolidone or poly(1-vinylpyrrolidone-co-vinyl acetate).

[0090] Method of preparation Methods of making these membranes are also disclosed herein. The methods of making the membranes can include depositing a selective polymer layer onto a support layer to form a selective layer disposed on the support layer. The selective polymer layer can include a selective polymer matrix and carbon nanotubes dispersed within the selective polymer matrix.

[0091] Optionally, the support layer may be pretreated prior to deposition of the selective polymer layer, e.g., to remove water or other adsorbed species using methods appropriate for the support and adsorbate. Examples of adsorbed species include, for example, water, alcohols, porogens, and surfactant templates.

[0092] The selective polymer layer may be prepared by first forming a coating solution that includes the components of the selective polymer matrix (e.g., hydrophilic polymer, amine-containing polymer, or combination thereof), hydrophilic polymer-coated carbon nanotubes, and optionally one or more additional components (e.g., amine-based transfer carriers, crosslinkers, base compounds, or combinations thereof) in a suitable solvent. One example of a suitable solvent is water. In some embodiments, the amount of water employed is in the range of 50% to 99%, based on the weight of the coating solution. The coating solution may then be used to form the selective polymer layer. For example, the coating solution may be later coated onto a support (e.g., a nanoporous gas-permeable membrane) using any suitable technique, and the solvent may be evaporated such that a nanoporous membrane is formed on the substrate. Examples of suitable coating techniques include, but are not limited to, "knife coating" or "dip coating." Knife coating involves the process of using a knife to spread the polymer solution across a flat substrate to form a thin film of the polymer solution of uniform thickness, followed by evaporation of the polymer solution solvent at ambient temperature or at temperatures up to about 100° C. or higher to obtain the fabricated membrane. Dip coating involves the process in which the polymer solution is contacted with a porous support. Excess solution can be drained from the support, and the polymer solution solvent is evaporated at ambient or elevated temperatures. The disclosed membranes can be formed in shapes such as hollow fibers, tubes, films, sheets, etc. In certain embodiments, the membranes can be configured in flat sheets, spiral wound, hollow fibers, or plate-and-frame configurations.

[0093] In some embodiments, the membrane may be heated at a temperature and for a time sufficient for crosslinking to occur. In one example, a crosslinking temperature ranging from 80° C. to 100° C. may be employed. In another example, crosslinking may occur for 1 to 72 hours. The resulting solution may be coated onto a support layer as described above, and the solvent may be allowed to evaporate. In some embodiments, after solvent removal, a higher degree of crosslinking of the polymer matrix occurs at about 100° C. to about 180° C., and crosslinking may occur for about 1 to about 72 hours.

[0094] Additives can be included in the selective polymer layer before forming the selective polymer layer to enhance the water retention capacity of the membrane.Suitable additives include, but are not limited to, polystyrene sulfonate-potassium salt, polystyrene sulfonate-sodium salt, polystyrene sulfonate-lithium salt, sulfonated polyphenylene oxide, alum, and combinations thereof.In one example, the additive includes polystyrene sulfonate-potassium salt.

[0095] In some embodiments, the methods for making these films can be scaled to industrial levels.

[0096] How to use The membranes disclosed herein can be used to separate gas mixtures. For example, methods are provided for separating a first gas from a feed gas that includes the first gas and one or more additional gases (e.g., at least a second gas). The methods can include contacting any of the disclosed membranes (e.g., on the side that includes the selective polymer) with a feed gas under conditions effective to allow the first gas to permeate through the membrane. In some embodiments, the methods can also include withdrawing a permeate containing at least the first gas from the back side of the membrane, where the first gas is selectively removed from the gas stream. The permeate can include at least the first gas in an increased concentration compared to the feed stream. The term "permeate" refers to the portion of the feed stream that is withdrawn at the back or second side of the membrane, excluding other fluids such as sweep gas or liquid that may be present on the second side of the membrane.

[0097] The membranes may be used to separate fluids at any suitable temperature, including temperatures of 100° C. or higher. For example, in some embodiments, the feed gas may have a temperature of 25° C. to 100° C. In other embodiments, the feed gas may have a temperature of 100° C. to 180° C. In some embodiments, a vacuum may be applied to the permeate side of the membrane to remove the first gas. In some embodiments, a sweep gas may be flowed across the permeate side of the membrane to remove the first gas. Any suitable sweep gas may be used. Suitable sweep gases include, for example, air, steam, nitrogen, argon, helium, and combinations thereof.

[0098] The first gas can include an acid gas. For example, the first gas can be carbon dioxide, hydrogen sulfide, hydrochloric acid, sulfur dioxide, sulfur trioxide, nitrogen oxides, or a combination thereof. In some embodiments, the membrane can be selective for carbon dioxide versus hydrogen, nitrogen, carbon monoxide, or a combination thereof. In some embodiments, the membrane can be selective for hydrogen sulfide versus hydrogen, nitrogen, carbon monoxide, or a combination thereof. In some embodiments, the membrane can be selective for hydrochloric acid gas versus hydrogen, nitrogen, carbon monoxide, or a combination thereof.

[0099] In certain embodiments, the first gas can include carbon dioxide and the second gas can include hydrogen. In certain embodiments, the first gas can include carbon dioxide and the second gas can include nitrogen.

[0100] The first gas or acid gas permeability can be at least 50 GPU (e.g., 75 GPU or more, 100 GPU or more, 150 GPU or more, 200 GPU or more, 250 GPU or more, 300 GPU or more, 350 GPU or more, 400 GPU or more, 450 GPU or more, 500 GPU or more, 550 GPU or more, 600 GPU or more, 650 GPU or more, 700 GPU or more, 750 GPU or more, 800 GPU or more, 850 GPU or more, 900 GPU or more, 950 GPU or more, 1000 GPU or more, 1100 GPU or more, 1200 GPU or more, 1300 GPU or more, or 1400 GPU or more) at 57° C. and 1 atmosphere of feed pressure.

[0101] The first gas or acid gas permeability can be 1500 or less (e.g., 1400 GPU or less, 1300 GPU or less, 1200 GPU or less, 1100 GPU or less, 1000 GPU or less, 950 GPU or less, 900 GPU or less, 850 GPU or less, 800 GPU or less, 750 GPU or less, 700 GPU or less, 650 GPU or less, 600 GPU or less, 550 GPU or less, 500 GPU or less, 450 GPU or less, 400 GPU or less, 350 GPU or less, 300 GPU or less, 250 GPU or less, 200 GPU or less, 150 GPU or less, 100 GPU or less, or 75 GPU or less) at 57° C. and 1 atmosphere feed pressure.

[0102] The permeability of the first gas or acid gas through the membrane can vary from any of the minimum values ​​described above to any of the maximum values ​​described above. For example, the permeability of the first gas or acid gas can be from 50 GPU to 1500 GPU at 57° C. and 1 atmosphere feed pressure (e.g., from 300 GPU to 1500 GPU at 120° C., or from 500 GPU to 1500 GPU at 57° C. and 1 atmosphere feed pressure).

[0103] The membrane may exhibit a first gas / second gas selectivity of at least 20 at 57° C. and 1 atmosphere feed pressure. In some embodiments, the membrane may exhibit a first gas / second gas selectivity of up to 300 at 57° C. and 1 atmosphere feed pressure. For example, the membrane may exhibit a first gas / second gas selectivity of 25 or more, 50 or more, 75 or more, 100 or more, 125 or more, 150 or more, 175 or more, 200 or more, 225 or more, 250 or more, or 275 or more at 57° C. and 1 atmosphere feed pressure. In some embodiments, the permeability and selectivity of the membrane to the first gas or acid gas may change at higher or lower temperatures.

[0104] By way of non-limiting illustration, examples of certain embodiments of the present disclosure are provided below. EXAMPLES

[0105] Example 1: Nanotube-reinforced membrane for CO2 / N2 separation using vacuum operation Abstract This example describes a membrane containing multi-walled carbon nanotubes (MWNTs) in an amine-containing polymer matrix for CO2 / N2 separation with vacuum on the permeate side. The polymer selective layer coated on the top surface of the highly permeable nanoporous support contains amino acid salts as mobile carriers in a polyamine matrix as fixed site carriers that facilitate the transport of CO2. The polymer-coated MWNTs are incorporated in the polymer selective layer as hard inorganic fillers. Both polyvinylpyrrolidone and poly(1-vinylpyrrolidone-co-vinyl acetate) can effectively coat on the hydrophobic surface of MWNTs to improve the dispersion of the polymer-coated MWNTs in the amine-containing selective layer. The polymer-coated MWNTs overcome the penetration of the selective layer into the nanoporous support under vacuum, and the MWNTs also reduce the compression of the membrane when the feed gas is compressed. These membranes are also applicable for CO2 / N2 separation by using a sweep gas on the permeate side.

[0106] Background technology Concerns about global warming have been growing since atmospheric CO2 concentrations exceeded 400 ppm in the past decade. Combustion of fossil fuels is one of the major causes of large CO2 emissions. Membrane technology has been proposed as a promising approach to capture CO2 from large stationary sources (e.g., flue gas from coal-fired power plants and flue gas from natural gas-fired power plants) followed by compression for geological sequestration or enhanced oil recovery. Several research efforts have been made to design a membrane process that can capture 90% of CO2 from power plant flue gas with at least 95% CO2 purity. US 7,964,020 [1] discloses a membrane gas separation process in which CO2 is concentrated by a vacuum membrane stage followed by a cryogenic distillation unit for further CO2 concentration. US9,216,390[2] discloses a membrane process in which CO2 can be concentrated to 95% purity by a vacuum membrane stage, where no further purification of CO2 downstream is required. The common element in these two examples is a vacuum membrane stage, where a vacuum of 0.2 atmospheres is pulled on the permeate side of the membrane to provide a transmembrane driving force. In this case, the membrane is subjected to a pressure difference from the feed to the permeate side. Although various membrane materials have been developed to minimize the CO2 capture cost based on the two above membrane processes, membrane performance in terms of CO2 permeability and CO2 / N2 selectivity has rarely been measured under vacuum operation mode. Sandru et al.[3] did indeed characterize their membrane performance by pulling a vacuum, but the CO2 permeability under vacuum was only half of that obtained by using a sweep gas on the permeate side. Zhao et al.[4] and Ansaloni et al.[5] used multi-walled carbon nanotubes incorporated into a polymer membrane as a mechanically reinforcing filler to address polymer compression caused by the feed-to-permeate pressure differential. However, the feed-to-permeate pressure differential in this example is generated by pulling a vacuum on the permeate side instead of pressurizing the feed gas as in references [4] and [5].This example of a polymeric membrane is an extension of the amine-containing composite membrane developed by Chen et al. [6], i.e., polyvinylamine (PVAm) was employed as the polymer matrix, however, a novel amino acid salt, e.g., 2-(1-piperazinyl)ethylamine sarcosinate (PZEA-Sar), was incorporated as a mobile carrier for CO2 transport. The membrane transport properties were measured by using a sweep gas on the permeate side. In the following example, it is shown that a vacuum on the permeate side leads to the penetration of the selective layer into the nanoporous substrate, thereby resulting in the degradation of the membrane performance. One approach to mitigate this penetration is to disperse multi-walled carbon nanotubes (MWNTs) in the polymer matrix as reinforcing nanofillers. However, nascent MWNTs were found to be incompatible with PVAm due to their hydrophobic nature. The viscosity of the polymer solution was significantly reduced even at very low MWNT loadings, which created difficulties in membrane coating for ultra-thin selective layers. It is shown that polyvinylpyrrolidone (PVP)-based polymers can effectively coat the hydrophobic surface of MWNTs, thus improving their dispersibility in PVAm. It is also shown that the mechanical strength of the polymeric selective layer can be improved by MWNTs at high feed-to-permeate pressure differentials.

[0107] material and method 2-(1-piperazinyl)ethylamine (PZEA, 99%), sarcosine (Sar, 98%), sodium dodecyl sulfate (SDS, 99%), and polyvinylpyrrolidone (PVP, 360 kDa) were purchased from Sigma-Aldrich (Milwaukee, WI). Poly(1-vinylpyrrolidone-co-vinyl acetate) (PVP3-co-VAc7, 3:7 molar ratio of VP:VAc, 50% in ethanol) was purchased from Fisher Scientific Inc. (Pittsburgh, PA). Poly(1-vinylpyrrolidone-co-vinyl acetate) (PVP7-co-VAc3, 7:3 molar ratio of VP:VAc, 50% in ethanol) was purchased from VWR International (Radnor, PA). MWNTs were provided as powder by Arkema Inc. (Philadelphia, PA) under the designation Graphistrength® C100 (0.1-10 μm length, 10-15 nm diameter, 5-12 membranes). The powder contained 90 wt% MWNTs, 6 wt% catalyst, and 4 wt% water. All chemicals were used as received without further purification. For gas permeation measurements, pre-purified CO2 and argon were purchased from Praxair Inc. (Danbury, CT).

[0108] With regard to the amine-containing polymer, it can be an amine polymer, such as, but not limited to, polyvinylamine (PVAm), polyallylamine, polyethyleneimine, copolymers, and blends thereof. The amine-containing polymer employed in the present invention is PVAm purified from a commercial product named Polymin® VX from BASF (Vandalia, IL). PVAm has a high weight average molecular weight of 2,000 kDa. The amine-containing polymer can have a weight average molecular weight of 300 to 10,000 kDa, but preferably higher than 1000 kDa.

[0109] In certain embodiments, an amino acid salt is blended into the amine-containing polymer to further facilitate CO transport. 2-(1-piperazinyl)ethylamine sarcosinate is used as an example in this example, but it can be the salt of any amino acid.

[0110] Polymer coating of MWNTs Polymer-coated MWNTs were prepared by suspending MWNT powder in 1 wt % aqueous SDS solution at 100 μg / mL MWNT content in a 45 mL conical centrifuge tube. The suspension was sonicated for 30 min with an ice-bath cooled sonication probe (Branson Sonifier® SFX150, Danbury, CT, 150 W output power). A 1 / 8" microtip probe at 70% amplitude was used to prevent tube damage. PVP, PVP7-co-VAc3, or PVP3-co-VAc7 were added into the dispersion to result in a 1 wt% mixture, which was incubated at 50°C for 16 h. The resulting mixture was centrifuged at 20,000 x g for 1 h (Eppendorf 5806, Westbury, NY) to form a gelatinous pellet. The pellet was collected and dispersed in RO (reverse osmosis) water at a concentration of 0.1 wt% by a sonication probe for 10 min and then centrifuged again. This centrifugation-dispersion cycle was repeated five times to remove excess residual polymer and SDS. After the final centrifugation, the polymer-coated MWNTs could form stable dispersions up to 1 wt%.

[0111] Coating solutions and membrane preparation MWNT-reinforced composite membranes were synthesized by the following steps. First, the purified PVAm solution was concentrated to 4 wt% by evaporating water at 50 °C under N2 purge. The polymer-coated MNWT dispersion with a concentration of 1 wt% was added dropwise to the concentrated PVAm solution under vigorous stirring by a 10 μL glass capillary tube, aiming for a MWNT loading of 0–6 wt% in the final total solids of the coating solution. The mixture was transferred to a 15 mL conical centrifuge tube, in which it was homogenized by a 1 / 8″ microtip sonication probe using 50% amplitude until uniformly dispersed. Sonication was performed in an ice bath.

[0112] An amino acid salt transfer carrier, PZEA-Sar, was synthesized by reacting a base, PZEA, with an amino acid, Sar. A stoichiometric amount of Sar was added into a 24 wt% aqueous solution of PZEA under vigorous mixing. The solution was mixed at room temperature for 2 hours before use. The chemical structure of PZEA-Sar is shown in Figure 1.

[0113] A certain amount of PZEA-Sar solution was incorporated into the dispersion to form the coating solution. After centrifugation at 8,000×g for 3 min to remove air bubbles, the coating solution was coated onto nanoporous polyethersulfone (PES) substrates by a GARDCO adjustable micrometer film applicator (Paul N. Gardner Company, Pompano Beach, FL) using a controlled gap setting. PES substrates with a surface average pore size of 32 nm were synthesized in-house [7]. Ideally, the coating solution should have a viscosity of >1100 cp with a total solids content of <15 wt% to form a defect-free selective layer with a thickness of about 170 nm. The membranes were dried in a fume hood at room temperature for at least 6 h before testing.

[0114] Gas Permeation Measurement The transport properties of the composite membranes were measured by a gas permeation unit shown in Figure 2, which allowed both sweep and vacuum mode operation on the permeate side. The synthesized membranes were loaded into a stainless steel rectangular permeation cell inside a temperature-controlled oven (Bemco Inc. Simi Valley, CA), which had a diameter of 2.7 cm. 2 The membrane had an effective area of ​​100 μm. The membrane was supported by a sintered stainless steel plate with an average pore size of 100 μm. A dry feed gas of 100 sccm containing 20% ​​CO2 and 80% N2 was used. The mixed gas was achieved by mixing two gas streams of CO2 and N2 controlled by two mass flow controllers (MFC1 and MFC2, Alicat Scientific, Tucson, AZ), respectively. When a sweep gas was used on the permeate side, a third mass flow controller (MFC3, Alicat Scientific, Tucson, AZ) was employed to pass 30 sccm of dry argon, which was directed to the permeate side by valve 1. The feed and sweep gases were each fully saturated with water vapor by bubbling 100 mL of water through two 500 mL stainless steel humidifiers (Swagelok, Westerville, OH) filled with 60% Raschig rings by volume. The temperature of the humidifier was controlled at 57°C, which is the typical flue gas temperature leaving a flue gas desulfurization (FGD) unit. Before reaching the permeation cell, the feed and sweep streams passed through two dry pressure vessels packed with Raschig rings to remove trapped water droplets. The feed and sweep pressures were controlled at 1-5 atm (absolute) and 1 psig, respectively, by two near-atmospheric regulators, PC1 and PC2. After the moisture was knocked out at room temperature by two respective condensers, the two outlet gases were sent to an Agilent 6890N gas chromatograph (GC, Agilent Technologies, Palo Alto, CA) for compositional analysis. The GC was equipped with a thermal conductivity detector and a SUPELCO Carboxen® 1004 Micropack GC column (Sigma-Aldrich, St. Louis, MO).

[0115] For vacuum mode, the permeate side of the permeate cell was connected to an Ebara MD1 vacuum diaphragm pump (Ebara Technologies, Inc., Sacramento, CA). The permeate pressure was precisely controlled at 0.1-0.9 atm by a vacuum regulator (VC, Alicat Scientific, Inc., Tucson, AZ). Before the permeate stream entered the vacuum pump, it was passed through a 1 L stainless steel water knockout vessel cooled to 0 °C with a chiller (Fisher Scientific, Hampton, NH) to remove moisture. 30 sccm of dry argon was directed by valve 1 to carry the vacuum pump effluent to the GC for compositional analysis.

[0116] The cross-sectional morphology of the membranes before and after testing was observed by scanning electron microscopy (SEM), which was performed using an FEI Nova Nano SEM400 (FEI Company, Hillsboro, OR).

[0117] Example 1A (Comparative) In this example, no carbon nanotubes were incorporated, so that the selective layer of the membrane contained only a polyamine, PVAm, and an amino acid salt, PZEA-Sar. The purpose was to demonstrate the performance of the different membranes when tested with argon sweep and vacuum on the permeate side.

[0118] 10 g of PVAm aqueous solution (1.5 wt%, viscosity of about 200 cp) was concentrated to 4 wt% by evaporating the water using N2 purge. 1.968 g of PZEA-Sar aqueous solution (43.19 wt%) was added to the concentrated PVAm solution to form a homogenous coating solution. The coating solution had a fixed to mobile carrier ratio of 15 / 85 (wt / wt), which makes the viscosity approximately 1400 cp. The coating solution was coated onto a nanoporous PES substrate with an average surface pore size of 32.0 nm using a GARDCO adjustable micrometer film applicator (Paul N. Gardner Company, Pompano Beach, FL). The membrane was allowed to dry overnight before gas permeation testing. A selective layer thickness of 170 nm was achieved by adjusting the gap setting of the film applicator. The membrane was tested with both argon sweep and vacuum. For the tests with argon sweep, the feed and permeate pressures were 1.5 and 1 psig, respectively, which corresponded to a feed to permeate pressure ratio of about 1. For the tests with vacuum, the feed pressure was 1.5 psig, while the permeate pressure was 0.2 atm, which resulted in a feed to permeate pressure ratio of about 5. The CO2 permeability and CO2 / N2 selectivity from the two different test conditions are shown in Table 1.

[0119] However, when a vacuum was pulled on the permeate side, the permeability reduced to 217 GPU. When the feed gas was saturated with water vapor at 57°C, the PVAm in the selective layer swelled greatly. The suction of the permeate dragged the selective layer into the pores of the nanoporous substrate, thereby increasing the mass transfer resistance of CO2. The degraded performance under vacuum was clearly attributed to the lack of mechanical strength of the selective layer. Cross-sectional SEM images of the membrane before and after vacuum testing are shown in Figure 3. Figure 3A shows that the membrane had an intact, well-defined selective layer of about 165 nm thickness before vacuum testing, while Figure 3B exhibits severe penetration of the membrane into the substrate pores after vacuum testing. [Table 1]

[0120] Example 1B (Comparative) In this example, nascent MWNTs were incorporated into the selective layer to improve mechanical strength. For 20 g of diluted PVAm solution (1.5 wt%), it was concentrated to 4 wt% by evaporating water under N2 purge. Then, 6.158 g of MWNT dispersion (1 wt%) was added to the concentrated PVAm solution under vigorous mixing. After this, the mixture was sonicated to redisperse. Then, the water introduced by the MWNT dispersion was evaporated by N2. Finally, 3.936 g of PZEA-Sar aqueous solution (43.19 wt%) was added to the dispersion to form a homogenous coating solution. However, the viscosity of the coating solution was only approximately 150 cp. The coating solution was coated onto the nanoporous PES substrate in the same manner as described in Example 1A. After drying overnight, the selective layer contained 3 wt% carbon nanotubes in total solids, and the PVAm to PZEA-Sar ratio was still 15 / 85 (wt / wt). The membrane was also tested with argon sweep and vacuum, respectively, and the transport results are shown in Table 2. The mechanical strength of the carbon nanotubes improved the CO2 permeability under vacuum to 577 GPU. However, it was still 296 GPU lower than that demonstrated by argon sweep. The lower permeability under vacuum was partially attributed to the low viscosity of the coating solution, which led to severe penetration during membrane coating. [Table 2]

[0121] Example 1C In this example, MWNTs coated with PVP3-co-VAc7 were incorporated. For 20 g of diluted PVAm solution (1.5 wt%), this was concentrated to 4 wt% by evaporating water under N2 purge. Then, 6.158 g of PVP3-co-VAc7 / MWNT dispersion (1 wt%) was added to the concentrated PVAm solution under vigorous mixing. After this, the mixture was sonicated to redisperse. Then, the water introduced by the MWNT dispersion was evaporated by N2. Finally, 3.936 g of PZEA-Sar aqueous solution (43.19 wt%) was added to the dispersion to form a homogenous coating solution. However, the viscosity of the coating solution was only approximately 979 cp. The coating solution was coated onto a nanoporous PES substrate in the same manner as described in Example 1A. After drying overnight, the selective layer contained 3 wt% carbon nanotubes in total solids and the PVAm to PZEA-Sar ratio was still 15 / 85 (wt / wt). The membrane was also tested with argon sweep and vacuum, respectively, and the transport results are shown in Table 3. The incorporation of PVP3-co-VAc7 / MWNTs led to a further improved CO2 permeability of 814 GPU, which was 597 GPU higher than the membrane without carbon nanotubes. [Table 3]

[0122] Example 1D In this example, MWNTs coated with PVP only were incorporated. For 20 g of diluted PVAm solution (1.5 wt%), this was concentrated to 4 wt% by evaporating water under N2 purge. Then, 6.158 g of PVP / MWNT dispersion (1 wt%) was added to the concentrated PVAm solution under vigorous mixing. After this, the mixture was sonicated to redisperse. Then, the water introduced by the MWNT dispersion was evaporated by N2. Finally, 3.936 g of PZEA-Sar aqueous solution (43.19 wt%) was added to the dispersion to form a homogenous coating solution. However, the viscosity of the coating solution was approximately 1313 cp. The coating solution was coated on a nanoporous PES substrate in the same manner as described in Example 1A. After drying overnight, the selective layer contained 3 wt% carbon nanotubes in total solids and the PVAm to PZEA-Sar ratio was still 15 / 85 (wt / wt). The membrane was also tested with argon sweep and vacuum, respectively, and the transport results are shown in Table 4. The incorporation of PVP / MWNTs led to further improved CO2 permeability of the 939GPU. The exhibited permeability was close to that characterized with argon sweep. [Table 4]

[0123] Example 1E In this example, MWNTs coated with PVP7-co-Vac3 were incorporated. For 20 g of diluted PVAm solution (1.5 wt%), this was concentrated to 4 wt% by evaporating water under N2 purge. Then, 6.158 g of PVP7-co-Vac3 / MWNT dispersion (1 wt%) was added to the concentrated PVAm solution under vigorous mixing. After this, the mixture was sonicated to redisperse. Then, the water introduced by the MWNT dispersion was evaporated by N2. Finally, 3.936 g of PZEA-Sar aqueous solution (43.19 wt%) was added to the dispersion to form a homogenous coating solution. However, the viscosity of the coating solution was approximately 1421 cp. The coating solution was coated on a nanoporous PES substrate in the same manner as described in Example 1A. After drying overnight, the selective layer contained 3 wt% carbon nanotubes in total solids, and the PVAm to PZEA-Sar ratio was still 15 / 85 (wt / wt). The membrane was also tested with argon sweep and vacuum, respectively, and the transport results are shown in Table 5. The incorporation of PVP7-co-Vac3 / MWNT led to further improved CO2 permeability of 970 GPU. The exhibited permeability nearly reproduced that characterized by argon sweep. Cross-sectional SEM images of the membrane before and after vacuum testing are shown in Figure 4A and Figure 4B. As can be seen from these figures, the selective layer after vacuum testing was clear with a thickness of about 165 nm, which was similar to the selective layer before testing. [Table 5]

[0124] Example 1F In this example, the PVP7-co-Vac3 / MWNT reinforced membrane (as described in Example 1E) was tested at high feed pressures of 1-5 atm (absolute). With a vacuum of 0.2 atm pulled on the permeate side, the feed-to-permeate pressure ratio was as high as 25. The transport performance of the membrane is shown in FIG. 5A. By increasing the feed pressure from 1 to 5 atm, the permeability decreased from 970 to 874 GPU. There are two possible causes for the reduced CO2 permeability. First, membrane compression may have occurred with the compression of the feed, which densified the polymer matrix, thereby reducing the permeability. Second, the CO2 permeability of the facilitated transport membrane may depend on the feed CO2 partial pressure, i.e., with higher CO2 partial pressure, the carrier saturation phenomenon occurred. To distinguish between these two effects, the membrane was tested at feed pressures of 1-5 atm, while the feed CO2 concentration was adjusted to maintain a constant CO2 partial pressure of 0.166 atm. As shown in Figure 5B, the CO2 permeability remained almost the same at different feed pressures, which confirmed that the support saturation phenomenon was the dominant factor. The dispersed MWNTs not only improved the stiffness of the selective layer to resist the bending deformation of the membrane caused by the vacuum suction, but also the compression of the feed with the vacuum suction was not enough to deform the enhanced selective layer.

[0125] References [1] R.W. Baker, G.W. Johannes, T.C. Merkel, H. Lin, R. Daniels, S. Thompson, "Gas Separation Process Using Membranes with Permeate Sweep to Remove CO2 from Combustion Gases," U.S. Patent No. 7,964,020, issued June 21, 2011. [2] W.S.W.Ho, H.Verweij, K.Shqau, K.Ramasubramanian, "Systems, Compositions, and Methods for Fluid Purification," U.S. Patent No. 9,216,390, issued December 22, 2015. [3] M. Sandru, S. H. Haukebo, M. B. Hagg, Composite hollow fiber membranes for CO2 capture, J. Memb. Sci. 346 (2010) 172 - 186。 [4] Y. Zhao, B. T. Jung, L. Ansaloni, W. S. W. Ho, Multiwalled carbon nanotube mixed matrix membranes containing amines for high pressure CO2 / H2 separation, J. Memb. Sci. 459 (2014) 233 - 243。 [5] L. Ansaloni, Y. Zhao, B. T. Jung, K. Ramasubramanian, M. G. Baschetti, W. S. W. Ho, Facilitated transport membranes containing amino - functionalized multi - walled carbon nanotubes for high - pressure CO2 separations, J. Memb. Sci. 490 (2015) 18 - 28。 [6] Y. Chen, W. S. W. Ho, High - molecular - weight polyvinylamine / piperazine glycinate membranes for CO2 capture from flue gas, J. Memb. Sci. (2016) 376 - 384. [7] D. Wu, L. Zhao, V. K. Vakharia, W. Salim, W. S. W. Ho, Synthesis and characterization of nanoporous polyethersulfone membrane as support for composite membrane in CO2 separation: From lab to pilot scale, J. Membr. Sci., 510 (2016) 58 - 71.

Example

[0126] Example 2: Amine-containing facilitated transport membranes for CO2 / N2 separation. Abstract This example relates to an amine-containing facilitated transport membrane with a mobile CO2 carrier for CO2 / N2 separation. In the selective layer of the membrane, an amine-containing polymer, which acts as a fixed site carrier, is used to form a polymer matrix in which polyvinylpyrrolidone-coated multi-walled carbon nanotubes are dispersed to enhance the mechanical properties of the polymeric material. Amino acid salts synthesized by reacting bases, e.g., piperazine, and 2-(1-piperazinyl)ethylamine, with amino acids, e.g., glycine, sarcosine, and 2-aminoisobutyric acid, are employed as mobile carriers to facilitate the transport of CO2. The present invention has demonstrated that these amino acid salts can function as effective mobile carriers to enhance the permeation of CO2 through ultrathin membranes at operating temperatures of 57-87°C. In the CO2 / N2 separation, a vacuum can be pulled or a sweep gas (e.g., water vapor-containing stream, air, or argon) can be used on the permeate side to provide or increase the driving force for the separation.

[0127] Background technology Since the Industrial Revolution, massive CO2 emissions from the combustion of fossil fuels have been the main reason for global warming. Post-combustion carbon capture encompasses the removal of CO2 from large stationary sources (e.g., flue gas from coal-fired and / or natural gas-fired power plants) and subsequently compressing the CO2 to 2215 psia for sequestration into geological formations or using it for enhanced oil recovery. Among all the technologies in the post-combustion portfolio, CO2-selective polymeric membranes have been proposed as a promising approach due to their energy efficiency, simplicity of operation, environmental friendliness, and ability to overcome thermodynamic solubility equilibrium limitations. A widely-involved approach for polymeric membrane synthesis is to coat an ultrathin selective layer of polymer onto a nanoporous support, typically an ultrafiltration membrane made from polysulfone, polyethersulfone, or polyetherimide. Several research efforts have been conducted in designing polymers with high CO2 permeability and suitable CO2 / N2 selectivity. On the one hand, polar functional groups such as ethylene oxide groups are incorporated to increase the physical CO2 solubility in the polymer matrix. The dissolved CO2 molecules diffuse through the membrane [1-3]. On the other hand, reactive functional groups and reactive compounds such as amines are used as mobile carriers or are attached to the polymer backbone as fixed site carriers to react reversibly with CO2 [4-6]. The chemical reaction enhances the permeation of CO2 through the membrane, and this type of membrane is referred to as a facilitated transport membrane.

[0128] For facilitated transport membranes, small molecules containing one or more amino group(s) can be incorporated into the polymer matrix as transport carriers. Such transport carriers react with CO2 on the feed side to form a reaction product. The reaction product then diffuses across the membrane and releases CO2 to the permeate side. Inspired by extensive research in aqueous amine absorption, aminoalcohols, e.g., monoethanolamine and diethanolamine, were among the first few small molecules employed to enhance CO2 flux through polyvinylamine (PVAm) or poly(vinyl alcohol) (PVA) membranes [7]. To increase the molar CO2 loading of the transport carrier, multiamines, e.g., ethylenediamine [7] and piperazine [8], were also proven as effective transport carriers. However, one possible drawback of multiamines is their relatively high volatility, which may result in carrier loss and thus reduced membrane permeability. To solve this problem, non-volatile amino acid salts have been synthesized by deprotonating amino acids such as 2-aminoisobutyric acid or glycine with a strong base, typically potassium hydroxide [9-11]. Recently, Chen and Ho reported a high-flux composite membrane with stable performance by using piperazine glycinate as a transport carrier in a polymer matrix formed by PVAm

[11] . In this example, novel amino acid salts by reacting a base, e.g., a cyclic secondary or tertiary amine, e.g., piperazine or 2-(1-piperazinyl)ethylamine, with an amino acid, e.g., glycine, sarcosine, and 2-aminoisobutyric acid, are employed as transport carriers to promote the transport of CO2. These amino acid salts act as more effective transport carriers than those reported to improve the permeation of CO2 through ultrathin membranes at operating temperatures of 57-87 °C.

[0129] material and method In this example, piperazine (99 wt%), 2-(1-piperazinyl)ethylamine (99 wt%), 2-aminoisobutyric acid (99 wt%), polyvinylpyrrolidone (360 kDa), sodium dodecyl sulfate (SDS, 99 wt%), and potassium hydroxide (85 wt%) were purchased from Sigma-Aldrich. Glycine (99 wt%) and sarcosine (99 wt%) were purchased from Acros Organics. These chemicals were used without further purification. With regard to the amine-containing polymer, it can be, but is not limited to, polyvinylamine (PVAm), polyallylamine, polyethyleneimine, copolymers, and blends thereof. The amine-containing polymer employed in the present invention was PVAm purified from a commercial product named Polymin® VX from BASF (Vandalia, IL). PVAm has a high weight average molecular weight of 2,000 kDa. The amine-containing polymer may have a weight average molecular weight of 300-3,000 kDa, but preferably higher than 1000 kDa. Carbon nanotubes may be dispersed in the PVAm to enhance the mechanical strength of the membrane. In the present invention, multi-walled carbon nanotubes (MWNTs) were used, which were named Graphistrength® C100 (0.1-10 μm length, 10-15 nm diameter) from Arkema Inc. (Philadelphia, PA). The length of the nanotubes may be in the range of 50 nm to 100 μm, but preferably 200 nm to 20 μm. The diameter of the nanotubes is unlimited, but advantageously ranges from 10 to 50 nm.

[0130] Carbon nanotube dispersion Commercially available carbon nanotubes are typically supplied as heavily entangled bundles, making them inherently difficult to disperse in water. Sonication was used in the present invention as an effective means to disperse carbon nanotubes in water. However, a physical coating of hydrophilic polyvinylpyrrolidone (PVP) is used to facilitate this process and stabilize the carbon nanotubes in the aqueous dispersion. The pristine MWNTs were dispersed in a 1 wt% SDS aqueous solution by sonication. The MWNT content in the dispersion was 1 wt%. PVP powder was added to the MWNT dispersion at a PVP to MWNT weight ratio of 1:1. The mixture was then incubated at 50°C for 5 hours to facilitate PVP coating. The resulting mixture was sonicated for 30 minutes and centrifuged at 10,000 rpm for 3 minutes. The supernatant was collected, where the PVP to MWNT weight ratio was approximately 1:2.

[0131] Coating solutions and membrane preparation PVP-coated MWNTs were added to a PVAm aqueous solution at a certain polymer concentration and carbon nanotube loading. The carbon nanotubes were dispersed in the polymer by performing another ultrasonic treatment. A certain amount of amino acid salt was then incorporated into the dispersion to form a coating solution. The coating solution was then coated onto a polyethersulfone (PES) nanoporous substrate using a "knife casting" technique. After the water was evaporated, the membrane was ready for gas permeation testing.

[0132] Gas Permeation Measurement Transport measurements were performed using a gas permeation setup as described below. Amine-containing membrane samples were loaded into a stainless steel rectangular permeation cell inside a temperature-controlled oven (Bemco Inc. Simi Valley, CA), which has an effective membrane area of ​​2.7 cm2. On the feed side, a 92 sccm binary gas mixture containing 20% ​​CO2 and 80% N2 was fully saturated with water vapor using a 500 mL stainless steel humidifier (Swagelok, Westerville, OH) filled with 60% volume of Raschig rings and 100 mL of water at 57°C. The feed pressure was controlled at 4 atm by a near-atmospheric regulator. On the permeate side, a vacuum was pulled to provide the transmembrane driving force. The composition of the retentate and permeate streams was analyzed by gas chromatography (GC) equipped with a thermal conductivity detector (Agilent Technologies, Palo Alto, CA). A SUPELCO Carboxen® 1004 Micropack GC column (Sigma-Aldrich, St. Louis, MO) was set up for analysis. The permeate side of the permeate cell was connected to a diaphragm vacuum pump (Ebara Corporation, Tokyo, Japan). The permeate pressure was precisely controlled at 0.2 atm by a vacuum regulator (Alicat Scientific, Inc., Tucson, AZ). Before the permeate stream entered the vacuum pump, it was passed through a 1 L stainless steel water knockout (Swagelok, Westerville, OH) cooled to 0° C. with a chiller (Fisher Scientific, Hampton, NH) to remove moisture. The vacuum pump output was conveyed to the GC for compositional analysis by a 30 sccm dry argon sweep.

[0133] Example 2A (Comparative) In this example, piperazine glycinate was synthesized and used as the transfer carrier. 1.061 g of glycine was dissolved in 5.002 g of DI water to form a 17.5 wt% aqueous solution. 1.217 g of piperazine was added to the glycine solution under vigorous mixing, resulting in a piperazine glycinate (PG) transfer carrier solution with a concentration of 30.978 wt%. Meanwhile, 20 g of aqueous PVAm solution (1.5 wt%, viscosity of about 200 cp) was concentrated to 4.5 wt% by evaporating the water using a N2 purge. A calculated amount of PVP-coated MWNTs was added dropwise to the concentrated PVAm solution under vigorous mixing, aiming for a 3 wt% MWNT loading in the total solids of the final selective layer. The mixture was then sonicated in a sonication bath to redisperse, which typically required 6 hours. Calculated amounts of PG solution were added to form coating solutions with PG to PVAm ratios of 65 / 35, 75 / 25, and 85 / 15 (wt / wt), respectively. The coating solutions were cast onto nanoporous PES substrates with an average surface pore size of about 32 nm using a GARDCO adjustable micrometer film applicator (Paul N. Gardner Company, Pompano Beach, FL). The membranes were allowed to dry overnight prior to gas permeation testing. A selective layer thickness of 170 nm was achieved by adjusting the gap setting of the film applicator. The membranes were tested using a feed pressure of 4 atm and a permeation vacuum of 0.2 atm. The CO2 permeability and CO2 / N2 selectivity with different PG contents are shown in Table 6. As can be seen, the membranes exhibited moderate CO2 permeability of about 800 GPU (1 GPU=10 -6 cm 3 (STP)·cm -2 ·Seconds -1 cmHg -1 Furthermore, the CO2 permeability increased with increasing PG content. The highest permeability of 839GPU was obtained with a PG to PVAm weight ratio of 85 / 15. [Table 6]

[0134] Example 2B - Membrane containing PZEA-Gly as a transport carrier In this example, piperazine was replaced with 2-(1-piperazinyl)ethylamine to react with glycine. First, 1.061 g of glycine was dissolved in 5.002 g of DI water to form a 17.5 wt% aqueous solution. 1.826 g of 2-(1-piperazinyl)ethylamine was added to the glycine solution under vigorous mixing, resulting in a 2-(1-piperazinyl)ethylamine glycinate (PZEA-Gly) mobile carrier solution with a concentration of 36.229 wt%. Meanwhile, 20 g of aqueous PVAm solution (1.5 wt%, viscosity of about 200 cp) was concentrated to 4.5 wt% by evaporating the water using a N2 purge. A calculated amount of PVP-coated MWNTs was added dropwise to the concentrated PVAm solution under vigorous mixing, aiming for a 3 wt% MWNT loading in the total solids of the final selective layer. After this, the mixture was sonicated in a sonication bath to redisperse. A calculated amount of PZEA-Gly solution was added to form coating solutions that had PZEA-Gly to PVAm ratios of 65 / 35, 75 / 25, and 85 / 15 (wt / wt), respectively. Three membranes were tested using a feed pressure of 4 atm and a permeation vacuum of 0.2 atm. The CO2 permeability and CO2 / N2 selectivity using different PZEA-Gly contents are shown in Table 7. As shown, an increase of 50-70 GPU in CO2 permeability was demonstrated with PZEA-Gly compared to PZ-Gly as the transfer carrier. The highest permeability was 911 GPU using a PZEA-Gly to PVAm weight ratio of 85 / 15. [Table 7]

[0135] Example 2C - Membrane containing PZEA-Sar as a transport carrier In this example, glycine was replaced with sarcosine to react with 2-(1-piperazinyl)ethylamine. First, 1.580 g of sarcosine was dissolved in 5.002 g of DI water to form a 24.0 wt% aqueous solution. 2.291 g of 2-(1-piperazinyl)ethylamine was added to the sarcosine solution under vigorous mixing, resulting in a 2-(1-piperazinyl)ethylamine sarcosinate (PZEA-Sar) mobile carrier solution with a concentration of 43.190 wt%. Meanwhile, 20 g of aqueous PVAm solution (1.5 wt%, viscosity of about 200 cp) was concentrated to 4.5 wt% by evaporating the water using a N2 purge. A calculated amount of PVP-coated MWNTs was added dropwise to the concentrated PVAm solution under vigorous mixing, aiming for a 3 wt% MWNT loading in the total solids of the final selective layer. After this, the mixture was sonicated in a sonication bath to redisperse. A calculated amount of PZEA-Sar solution was added to form coating solutions with PZEA-Sar to PVAm ratios of 65 / 35, 75 / 25, and 85 / 15 (wt / wt), respectively. The membranes were tested with a feed pressure of 4 atm and a permeation vacuum of 0.2 atm. The CO2 permeability and CO2 / N2 selectivity with different PZEA-Sar contents are shown in Table 8. As shown, an increase of approximately 15 GPU in CO2 permeability was demonstrated by PZEA-Sar compared to PZEA-Gly as a transfer carrier. The highest permeability was 926 GPU with a PZEA-Sar to PVAm weight ratio of 85 / 15. [Table 8]

[0136] Example 2D - Membranes containing PZEA-AIBA and PZEA-Sar as transport carriers In this example, a portion of sarcosine was replaced with 2-aminoisobutyric acid to react with 2-(1-piperazinyl)ethylamine with the aid of KOH. First, 1.250 g of 2-(1-piperazinyl)ethylamine was dissolved in 5.002 g of DI water to form a 25.0 wt% aqueous solution. A KOH aqueous solution having a concentration of 1 M was added until the pH value reached 12. After this, 0.998 g of 2-aminoisobutyric acid was added, and the mixture was kept mixed vigorously until the 2-aminoisobutyric acid was completely dissolved, and the solution was designated as PZEA-AIBA. Meanwhile, 1.580 g of sarcosine was dissolved in 5.002 g of DI water to form a 24.0 wt% aqueous solution. To the sarcosine solution, 2.291 g of 2-(1-piperazinyl)ethylamine was added under vigorous mixing, resulting in a PZEA-Sar transfer carrier with a concentration of 43.190 wt%. Then, 3.228 g of this PZEA-Sar solution was gradually added to the PZEA-AIBA solution, resulting in a PZEA-AIBA / PZEA-Sar transfer carrier solution with a molar ratio of AIBA to sarcosine of 60 / 40. Meanwhile, 20 g of aqueous PVAm solution (1.5 wt%, viscosity of about 200 cp) was concentrated to 4.5 wt% by evaporating water using a N2 purge. To the concentrated PVAm solution, a calculated amount of PVP-coated MWNTs was added dropwise under vigorous mixing, aiming for a MWNT loading of 3 wt% in the total solids of the final selective layer. The mixture was then sonicated in a sonication bath to redisperse. A calculated amount of PZEA-AIBA / PZEA-Sar solution was added to form coating solutions with PZEA-AIBA / PZEA-Sar to PVAm ratios of 65 / 35, 75 / 25, and 85 / 15 (wt / wt), respectively. The membranes were tested with a feed pressure of 4 atm and a permeate vacuum of 0.2 atm. The CO2 permeability and CO2 / N2 selectivity with different PZEA-AIBA / PZEA-Sar contents are shown in Table 9. As shown, an increase of approximately 15 GPU in CO2 permeability was demonstrated by PZEA-AIBA / PZEA-Sar compared to PZEA-Sar as the transfer carrier. The highest permeability was 944 GPU with a PZEA-AIBA / PZEA-Sar to PVAm weight ratio of 85 / 15. [Table 9]

[0137] Example 2E - Membranes containing PZEA-AIBA and PZEA-Sar as transport carriers at various temperatures In this example, the membrane with 85 / 15 PZEA-AIBA / PZEA-Sar to PVAm ratio synthesized in Example 2D was tested at higher temperatures in the range of 67-87°C instead of 57°C. The feed pressure was kept at 4 atm before passing through the membrane, and the feed gas was fully saturated with water vapor at the corresponding test temperature. However, the vacuum pressure on the permeate side was kept at 0.01 atm higher than the water saturation pressure at the corresponding temperature to avoid condensation. The CO2 permeability and CO2 / N2 selectivity at different temperatures are shown in Table 10. As shown, the CO2 permeability was strongly dependent on the operating temperature. A temperature of 67°C increased the permeability to 1468 GPU with a high selectivity of 162. Further increase in temperature to 77 and 87°C resulted in even higher permeabilities of 2102 and 2957 GPU, respectively. It is noted that the selectivity at 77 and 87°C was lower than that at lower temperatures. However, these selectivities were still significantly higher than those exhibited by membranes without facilitated transport, which are typically less than 20 at high temperatures [1-3]. [Table 10] References [1] Y. Chen, B. Wang, L. Zhao, P. Dutta, WSWHo, New Pebax (registered trademark) / zeolite Y composite membranes for CO2 capture from flue gas, J. Membr. Sci. 495 (2015) 415-423. [2]W.Yave,A.Car,S.S.Funari,S.P.Nunes,K.-V.Peinemann,CO2-philic polymer membrane with extremely high separation performance,Macromolecules 43(2009)326-333. [3]W.Yave,A.Car,J.Wind,K.-V.Peinemann,Nanometric thin film membranes manufactured on square meter scale:Ultra-thin films for CO2capture,Nanotechnology 21(2010)395301. [4]X.He,M.-B.Hagg,Energy efficient process for CO2capture from flue gas with novel fixed-site-carrier membranes,Energy Procedia 63(2014)174-185. [5]T.-J.Kim,H.Vralstad,M.Sandru,M.-B.Hagg,Separation performance of PVAm composite membrane for CO2capture at various pH levels,J.Membr.Sci.428(2013)218-224。 [6]M.Sandru,S.H.Haukebo,M.-B.Hagg,Composite hollow fiber membranes for CO2capture,J.Membr.Sci.346(2010)172-186。 [7]Z.Qiao,Z.Wang,S.Yuan,J.Wang,S.Wang,Preparation and characterization of small molecular amine modified PVAm membranes for CO2 / H2separation,J.Membr.Sci.475(2015)290-302。 [8]Z.Qiao,Z.Wang,C.Zhang,S.Yuan,Y.Zhu,J.Wang,S.Wang,PVAm-PIP / PS composite membrane with high performance for CO2 / N2separation,AIChE J.59(2013)215-228. [9]J.Zou,W.S.W.Ho,CO2-selective polymeric membranes containing amines in crosslinked poly(vinyl alcohol),J.Membr.Sci.286(2006)310-321。

[10] J.Huang,J.Zou,W.S.W.Ho,Carbon dioxide capture using a CO2-selective facilitated transport membrane,Ind.Eng.Chem.Res.47(2008)1261-1267。

[11] Y.Chen,W.S.W.Ho,High-molecular-weight polyvinylamine / piperazine glycinate membranes for CO2capture from flue gas,J.Membr.Sci.(2016)376-384.

[0138] The apparatus, systems, and methods of the appended claims are not limited in scope by the specific apparatus, systems, and methods described herein, which are intended as illustrations of some aspects of the claims. Any apparatus, systems, and methods that are functionally equivalent are intended to be included within the scope of the claims. Various modifications of the apparatus, systems, and methods in addition to those shown and described herein are intended to be included within the scope of the appended claims. Furthermore, only certain representative apparatus, systems, and method steps disclosed herein are specifically described, but other combinations of apparatus, systems, and method steps are also intended to be included within the scope of the appended claims, even if not specifically recited. Thus, although combinations of steps, elements, components, or structures may be referred to explicitly or infra in this specification, other combinations of steps, elements, components, and structures are included even if not explicitly stated.

[0139] As used herein, the term "comprising" and variations thereof are used synonymously with the term "including" and variations thereof, and are open and non-limiting terms. Although the terms "comprising" and "including" have been used herein to describe various embodiments, more specific embodiments of the present invention can be provided and are also disclosed by using the terms "consisting essentially of" and "consisting of" instead of "comprising" and "including". Unless otherwise noted, all numbers expressing shapes, dimensions, and the like used in the specification and claims should at least not be understood as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, but should be interpreted in light of significant digits and ordinary rounding techniques.

[0140] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the disclosed invention belongs. Publications cited herein and the materials for which they are cited are specifically incorporated by reference.

Claims

1. A membrane, The support base and a selective polymer layer disposed on the support layer; the selective polymer layer comprises a selective polymer matrix and carbon nanotubes dispersed within the selective polymer matrix; the selective polymer matrix comprises an amine-containing polymer and a transfer carrier comprising 2-(1-piperazinyl)ethylamine sarcosine salt (PZEA-Sar) and 2-(1-piperazinyl)ethylamine aminoisobutyric acid (PZEA-AIBA); The carbon nanotubes are coated with a hydrophilic polymer.

2. The selective polymer matrix has a CO concentration of at least 10 at 57° C. and 1 atm feed pressure. 2 :N 2 The membrane of claim 1 having selectivity.

3. The selective polymer matrix has a CO concentration of 10 to 500 at 57° C. and 1 atm feed pressure. 2 :N 2 The membrane of claim 1 or 2, which has selectivity.

4. The selective polymer matrix has a CO concentration of 10 to 350 at 57° C. and 1 atm feed pressure. 2 :N 2 The membrane according to any one of claims 1 to 3, which has selectivity.

5. 2. The membrane of claim 1, wherein the amine-containing polymer is selected from the group consisting of polyvinylamine, polyallylamine, polyethyleneimine, poly-N-isopropylallylamine, poly-N-tert-butylallylamine, poly-N-1,2-dimethylpropylallylamine, poly-N-methylallylamine, poly-N,N-dimethylallylamine, poly-2-vinylpiperidine, poly-4-vinylpiperidine, polyaminostyrene, chitosan, copolymers, and blends thereof.

6. 6. The membrane of claim 5, wherein the amine-containing polymer comprises polyvinylamine.

7. The membrane of any one of claims 1 to 6, wherein the selective polymer matrix further comprises a hydrophilic polymer.

8. The membrane of claim 7, wherein the hydrophilic polymer comprises a polymer selected from the group consisting of polyvinyl alcohol, polyvinyl acetate, polyethylene oxide, polyvinylpyrrolidone, polyacrylamine, polyamine, polysiloxane, copolymers thereof, and blends thereof.

9. The membrane of claim 8, wherein the hydrophilic polymer comprises a polymer selected from the group consisting of polyallylamine, polyvinylamine, or polyethyleneimine, copolymers thereof, and blends thereof.

10. The membrane of any one of claims 1 to 9, wherein the selective polymer matrix further comprises a cross-linking agent.

11. 11. The membrane of claim 10, wherein the crosslinking agent comprises a compound selected from the group consisting of formaldehyde, glutaraldehyde, maleic anhydride, glyoxal, divinyl sulfone, toluene diisocyanate, trimethylol melamine, terephthalate aldehyde, epichlorohydrin, vinyl acrylate, and combinations thereof.

12. The membrane of any one of claims 1 to 11, wherein the carbon nanotubes comprise single-walled carbon nanotubes.

13. The membrane of any one of claims 1 to 12, wherein the carbon nanotubes comprise multi-walled carbon nanotubes.

14. The membrane of any of claims 1 to 13, wherein the selective polymer layer comprises 0.5% to 5% by weight of carbon nanotubes, based on the total dry weight of the selective polymer layer.

15. The membrane according to any one of claims 1 to 14, wherein the carbon nanotubes have an average diameter of from 10 nm to 50 nm.

16. The membrane according to any one of claims 1 to 15, wherein the carbon nanotubes have an average length of from 50 nm to 20 μm.

17. The membrane of any of claims 1 to 16, wherein the carbon nanotubes comprise sidewall-functionalized carbon nanotubes.

18. 20. The membrane of claim 17, wherein the sidewall-functionalized carbon nanotubes comprise hydroxy-functionalized carbon nanotubes, carboxy-functionalized carbon nanotubes, amine-functionalized carbon nanotubes, or a combination thereof.

19. The membrane of any of claims 1 to 18, wherein the support layer comprises a gas permeable polymer.

20. 20. The membrane of claim 19, wherein the gas permeable polymer comprises a polymer selected from polyamides, polyimides, polypyrrolones, polyesters, sulfone-based polymers, nitrile-based polymers, polymeric organosilicones, fluorinated polymers, polyolefins, copolymers thereof, and blends thereof.

21. 21. The membrane of claim 19 or 20, wherein the gas permeable polymer comprises polyethersulfone or polysulfone.

22. The membrane of any of claims 1 to 21, wherein the support layer comprises a gas permeable polymer disposed on a base.

23. 23. The membrane of claim 22, wherein the base comprises a nonwoven fabric.

24. 24. The membrane of claim 23, wherein the nonwoven fabric comprises fibers formed from polyester.

25. The membrane of any of claims 1 to 24, wherein the membrane further comprises a permeable layer disposed between the support layer and the selective polymer layer.

26. 26. The membrane of claim 25, wherein the permeable layer comprises a gas permeable polymer selected from poly(dimethylsiloxane), poly(trimethylsilylpropyne), poly(4-methyl-1-pentene), copolymers thereof, and blends thereof.

27. 27. The membrane of any of claims 1 to 26, wherein the membrane is configured in a flat sheet, spiral wound, hollow fiber, or plate and frame configuration.

28. The membrane of any one of claims 1 to 27, wherein the membrane is selectively permeable to acid gases.

29. 29. The membrane of any one of claims 1 to 28, wherein the membrane is selectively permeable to a fluid selected from the group consisting of carbon dioxide, hydrogen sulfide, sulfur dioxide, sulfur trioxide, nitrogen oxides, hydrogen chloride, water, and combinations thereof.

30. 30. A method for separating a first gas from a feed gas stream, comprising contacting a membrane as defined by any of claims 1 to 29 with the feed gas stream containing said first gas to allow transmembrane permeation of said first gas.

31. 31. The method of claim 30, wherein the feed gas comprises hydrogen, carbon dioxide, hydrogen sulfide, hydrogen chloride, carbon monoxide, nitrogen, methane, water, oxides of sulfur, oxides of nitrogen, or combinations thereof.

32. 32. The method of claim 30 or 31, wherein the first gas is selected from carbon dioxide, hydrogen sulfide, hydrogen chloride, and combinations thereof.

33. the feed gas comprises a second gas selected from the group consisting of nitrogen, hydrogen, carbon monoxide, and combinations thereof; The method of any of claims 30-32, wherein the membrane exhibits a first gas / second gas selectivity of 20-300 at 57°C and 1 atmosphere feed pressure.

34. The method of any of claims 30-33, wherein the membrane comprises a feed side and a permeate side, the method further comprising applying a vacuum to the permeate side of the membrane to remove the first gas.

35. 35. The method of any of claims 30-34, wherein the membrane comprises a feed side and a permeate side, the method further comprising flowing a sweep gas across the permeate side of the membrane to remove the first gas.

36. 36. The method of claim 35, wherein the scavenging gas comprises a gas selected from the group consisting of air, water vapor, nitrogen, argon, helium, and combinations thereof.

37. The method according to any of claims 30 to 36, wherein the feed gas has a temperature of from 25°C to 100°C.

38. The method of any of claims 30 to 37, wherein the feed gas has a temperature of at least 100°C.

39. 1. A method of making a membrane comprising depositing a selective polymer layer on a support layer, the selective polymer layer comprising a selective polymer matrix and carbon nanotubes dispersed within the selective polymer matrix; the selective polymer matrix comprises an amine-containing polymer and a transfer carrier comprising 2-(1-piperazinyl)ethylamine sarcosine salt (PZEA-Sar) and 2-(1-piperazinyl)ethylamine aminoisobutyric acid (PZEA-AIBA); The method, wherein the carbon nanotubes are coated with a hydrophilic polymer.

Citation Information

Patent Citations

  • Polyvinylamine composite functional membrane with lamella sieving channel and preparation method and application of polyvinylamine composite functional membran

    CN107469635A

  • Carbon dioxide separation member, method for manufacturing the same, and carbon dioxide separation module

    JP2013027841A

  • Materials containing grafted nanotubes or nanowires in a matrix, methods for preparing the same, and applications thereof.

    JP2013545825A

  • Composite thin film incorporating carbon nanotubes

    JP2014500131A